SASTRA ANAK DI USIA AWAL DAN LITERASI - Nurgiyantoro, Burhan (Diksi, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAcUAAAJ8CAIAAAAAji3zAAAgAElEQVR4nOydd1QVyda3W0BHMecAKjoDmAAFFAMoKqCCCREkZ4mSoyAKIoKI5CBIUnLOOQoIiCSRnCRnOIQDnNzfH/VNr/Me1HHu5b0z895+FssF3dWVuutXu3btbiFDy6foz7L8GD20N7awuXPnzsULAopKKmaPnhpY2i39MbS0+8ur+vf8MXtkr6isKiIsdOP69RsoKP9AoPs6hujPMv0YaOvo6Ok9MDAw0Hugq6Wt+1fX5x/2o6X9QO+Brr6+gT4Kyj8TyA1lWXH///zV9fhn4u6OdCAKyj8PyNrKCv1Zrh8a/vL6/LN+UFD+6UAjKCgoKCjLAQSjoKCgoCwHy6OnFApluRKTyeRlKeXf52eKo1Aoy1UrJB/K74A/yWTyD/rkJ2tCoVDIZPKPq0pT6B+m+XFxSw/+YQV+XNzPn6JJ9u88UUtL+Zl+/sNaofxfZdns0/n5+fT0dAsLC319fTMzs4iIiNra2sbGxomJCZqUFAqlp6enra1tfn7+m1mRyeSsrCw7Ozt9ff3nz58XFBRUVlY2NjaSyeS+vr7MzMzw8PCQkJCIiIiUlJT09PSUlJR37969e/cuOjq6sLBwaGiopaXl7du3SUlJ6enp6enpCQkJ4eHhYWFh8fHx5eXl09PTP2gIFosdHR2dnZ39eT2dnJxsaWlZWFigOTs+Pp6cnBwfH19UVFRSUtLZ2UkikcCpxcXFpKSkyMjIhISElJSUlpYWGj0lEAhzc3NYLJZmAC8sLFRUVLx79y4tLa20tLS7uzsrK6u0tJREIhEIhJaWlqSkpOTk5NTU1Hfv3lVXV1PnSaFQSkpKkpOTOzo6BgYG+vr62tra2traOjo6aFSATCZ//fq1paWlt7d3YGCgv7+/vb29qalpbm4OqQyJRJqYmGhtbe3q6hoYGBgYGOju7m5tbR0dHSUQCMPDwx0dHT09PR0dHd3d3XNzc+AqHA7X3Nycm5uL1G1mZoZAIIyPj3d2dn79+hXJqqWlBTSfpsNnZmbAwZ+8QaC3sVgs0rTh4eHu7m4kzeTk5NTU1MzMDHUnYLHYr1+/EolEcH8nJiamp6eX3o5vFofFYlFV/e9kefQUh8MFBgYKCgqeOnXqypUroqKi4uLi169fd3R07O3tRZIhD+Lr16+1tLTKy8uXZjU4OOjr6wsyuXLlyt27d+/evSssLOzt7U0mk1NSUgQEBKSkpBwcHHR0dM6cOXP06FE+Pj4TExNjY+Nr166JiYklJyfX1taamJhwc3MfPXr06NGjV69e1dbW1tTUFBMTExERsbS0zMvLQwYYDRUVFW5ubiUlJT/TcNCiyspKfX398vJyRC4Bw8PDz549ExERERAQEBAQUFJSQrKdn593cXG5fPnyyZMntbW1KysrafIcGRl5+/ZtVFQUTYlzc3PZ2dnq6uocHBwXLlxQUVFRV1dPSEgAevrx40dlZWVWVlZWVlZBQcGYmBiano+MjJSSklJUVNTW1tbX13/16pWzs7O2tratrW1ubu7MzAySPjc318bGRldXV0tLS0dHx9bWNioqanJyEqkJHo9vaWkJDg42MTHR1NTU0tKysLAIDg6ura3F4XCVlZUvX77U0tIyMTFJTEwEF9bU1Dg7OxsZGamrq6upqT179iwwMDAyMhKDwbS2tnp6eoLiNDU1DQ0NAwIClk7GBAIhMjKyvLwch8P9pLU7MzOTkJCQn58P/iQSiXl5eSYmJk5OTpGRkb6+vsHBwZ2dnV++fPH39/f394+MjAwLC3v58uXr168XFxdhGC4tLXV0dDQ1NY2IiKDOuaSkpK6ujqa42dnZ2NjYFy9eREZGRkZGRkRExMbGtra2EgiE79Wwv78/MTExPDw8IiIiMjIyKCjI29vbz88vISGhoaGBSCT+oHV4PL65uZl6egAsLCzk5ua+efMmKyvr48ePra2tyKnR0dGMjIyQkJDQ0NDQ0NDBwUHqCycmJlJTU4OCgtLT09PS0kJDQ4ODg6urq2mqMTY2lpKSAgyU6upqYLuASTotLS07Ozs7O7uoqKiysrKqqqqsrCwnJycjIyMsLKysrGx0dLSwsDAkJKSqqqqqqqq8vDwvLy8yMjI8PDwvL6+goKCwsBAUl5OTExcXBzKprKwsKCjIyckpKCiorq7u6emhGW5L6erqQh5pGiYmJhITE728vLy9vZOSklpaWvLz80dGRigUSl5eXnBwcEVFRXV1dWVlZVxcXEpKCk0vfY/l0dPS0tLffvuNh4fn8+fPMAxTKJSIiIiDBw/eu3eP+kaCSZtEIqmpqa1fv97R0XFpVhEREWvXrr106dLo6ChotoWFxZYtW0xMTGZmZuzt7U+fPh0bGwvDcFpaGisrKwRBBw4caG9v7+/v9/T0ZGdnf/jwIQzDHR0dx44dgyAIgiBpaekPHz7U1dW9fPmSjY0NgqDDhw8XFBRQr0CRXxwdHdnY2KysrPB4/M+0nUwmh4aG7tmzx8bGZnZ2Fv6fdlN3d7eenh4dHR2oiaSkZFdXFzg1NTWlqal54cKF6OjopWXl5+dzcXFduXKF2opHcs7Ozl6xYgXI8+nTp8jlk5OTioqKO3fuvHz5sq+vL/VkBpienn78+PGqVasgCNq0aZOPj8+bN28UFRU3bNiwa9euly9fDgwMgJRfvnyxtrbeu3cvBEFr1qzR1dWtqqqirieRSBwaGsrKyhIQEAA1uXTpUlZWVnd3N4lEamtrs7GxWbdu3eXLl8vKyhYXF5uamq5du3bo0CEjI6PAwEAzM7PDhw+DuzMyMjI2NhYUFMTLywuy4uDgSExMpDb5QdsHBweFhISUlJQ6Ozt/5u7AMFxQUHDu3Dlzc3Pkfn348EFSUhJ0ID09va6u7sjISGNjo7KyMtKrZ86cCQsLAyJYXl7Ozc1NR0f35MkTJNv5+Xl+fn4lJSWaezc0NOTh4cHOzg79zu3bt9PT07+3GqNQKFVVVcrKyocOHQLpt2zZwsHBcerUKV5eXlFRUX9//66uru8ZvNXV1Xfv3nVycqI5PjU19ejRox07dmzfvp2Pj09KSqq8vBw0p7m5WU1NbfXq1fT09Pz8/LW1tdRPbEdHh46Ozvbt23fs2LFx48aVK1eePn06KCgIh8NR59/S0qKiosLOzs7Dw3P+/Pljx47p6OgUFhY6ODjs2bNHVlbW0tJSQUHh4sWL586du3HjxsOHD9XV1Tdu3Hjy5Mn09HR7e/ujR48KCAjw8/NfvXpVX19fSkpKTEzs5s2b+/fvP3HiBFhEPnz48NKlS1euXDl37tzFixcVFRX19PQUFBTExMRUVVUDAgLa2tq+2S1kMrmlpUVTUxMsg2j8VP39/Y8ePeLk5Dxx4sSJEycuX74sKSm5f//+nJwcMplsY2PDxcUlJCR0/vz5M2fOnDx5UlNTs7a29psF0bAMekomk588ecLIyHjlypUvX76Agzgczs3N7d69e9nZ2TTpGxsbz58/D0GQjIzM0hnGw8MDgqBbt25NTU2BI2NjYxISElJSUn19fWZmZq6uruPj4zAMJyUlgaeWlZUVGDJYLFZaWlpXVxeG4cHBQQkJCTA87t+/39fXB8Pw+Pj4s2fP1qxZA2Ro6dw1PT0tJSUFpIF6JvgBPT09ampqEARdvHhxaGgI/p96isPhYmJiODk5161bB0HQ6tWrDQ0NwQikUCiPHj0yMTEBzwSNtfX8+fMVK1bw8vJWVVVRPwpgXNXU1GzevBmCoBUrViBG08LCQnJysqCgoJWVVW9vL4lE+qYFl5GRceLEiRUrVjAzM/f29hKJxNnZ2YcPH65cuXL9+vW6uroYDAaU1djYeOvWLQiCmJiYYmJiwIii8UtgsVhDQ0NGRkYIgvT09JApikwmV1ZWXrp0yc7Ojkwmz83Nubu7b9u2TU1Nrb+/H4ZhAoHw/v17AQGBe/fugSNEItHOzg70kp6eHjBpqZtAJpPz8/MPHjzIzs5eUFDwM3cHhmFnZ+dffvlFVlYW8TmAuoFpgJmZ2dXVFRwcHR0VFxeno6Ojo6PT1NREHk4KhSInJyckJASeIkBhYeGhQ4cuXLjQ0NCAHER8Ne7u7mAS3bVrV2NjI5FI/Kb7GNxQEok0MjLy/PlzoKcGBgb9/f0YDMbV1XX79u3r1q1TUVFZOjUCnJyc6OjowDNPkzMOh3N2dgZ5rlq1SkJCoqmpCbS0qalJUVHxxo0bLS0tJBKJum5kMnl2dtbU1HTr1q0QBF27dg0Y1zSODuB8MzQ03LhxIx0dnZaW1tjYWF1dnZiY2JkzZ/Ly8nA4nKur686dO0EmOByus7PT0NCQmZk5NDQUj8cnJCRs3LgRTF0NDQ0LCwv9/f2+vr6//vorOzs7GOM4HC4lJeXMmTMrVqzYv39/cnJyd3d3UlLS6dOnV69e/csvv8jIyHzT8MdgMNbW1tu2bUtLS4P/p+8ej8dbWlquWrXK3Nx8cXFxdnY2MTHx+PHjEASlpqaCQnNzc48ePUpHR0dPT+/j4zM7O/uHtjBgGfSURCJZWVkdPXqUn5//2bNnra2tiCmRn5+PmGNIYicnp+3bt0MQdOrUqYqKCprcvL29wVPo5eWFSGpoaKitrS2BQJiYmEDW6QkJCUBP2djYQO/DMFxdXQ1mpP7+/nv37tHT00MQpKGhgZhdZWVl7Ozsq1evtrCwAPJHTWpq6rlz51atWsXHxxcfH/8DPx1yMD4+no2NbeXKlbt27VrqwZifn09LS/Pz87OxsQHmGCsrK7IMt7GxsbCw6OjooMmzt7dXWVl506ZNZ8+edXZ2RkwD5Jnu7u4WFRWlp6dnZmYGK9nZ2dmQkBA5ObnY2FggiN+jurpaTU1t+/bt+/fvHx4eBgcrKysvXrwIpDM2NhYofmdnp6SkJARB+/btS0pKonmkQE0IBIKZmdn69eshCDI2NqY+hcfjbWxsXr9+DcPw2NiYlZXVvn37ZGRkqG2KzMxMXV3dr1+/gj9fvHgB6hAZGQlWfNSdPzMz4+LiwsfHx8rKGhAQAOrzY4fm+Pj4vXv3Nm7ceOfOnZycHOrK29nZ/fbbb4cOHdLR0UHGZEZGBg8PD5hQkYcKi8VaW1u7u7sjl5NIpMePH+/du5eNjS0oKIimT2AYzsnJASuh8+fPj4yMfK+eyMHFxUUPDw8GBgYIgqysrMBCp6OjQ1NTc8OGDXv37g0JCQHOB2pGR0fBDVJUVKTWeoTY2Njdu3dzcHBs2bJl165drq6uYFIZHx9/8+aNq6srMCmW1s3W1vbEiRObNm0yMjKiqSrC4uJiUFDQqVOnNmzY4OHhAcNwcXGxvLx8ZGQk6E9PT88dO3YAPQWXTE5OysnJvXv3Dobh2traEydOQBB0/fp1UPne3t6urq74+HgJCQmk85ubm3V1dVevXn3s2DFgNuHxeCcnp8OHD69du5afn7+mpmZpwzs7OwUEBLZu3WpnZzc2NkZ9CovFXrt2jZGRMTQ0FBwhEolZWVnMzMxg4QvDcF1dnaCgICMj48qVK9+/f780/++xDHpKoVBCQkKOHj3KyMi4ffv2CxcuhISEgO4gkUjAow9SEgiE9PT0mzdv7ty5c+XKlYyMjNra2jQLmZCQEGBU7tq1S1ZWNjc3FxhByMhHSExMXKqn8O/PdF9fn6SkJLARED2dn5/38fEBs6K7uzvNEmZqakpBQWHLli2MjIzr1q2Tl5cHPofvtRqG4ZmZGWdnZ/DQrFq1ytramromMAwvLCzEx8dbWFhUVVU9fPgQgiA6OjoeHp6SkhJgjpmZmbW3t4PESFfY2NiwsbGxsLBs2LDh1KlTiNwg9Pb2SklJ0dPT//rrr8CZaGdnd+fOnfz8/KWjjobc3FwwZ+zbtw+ZZiYmJnR1dRGnBJCA9vb2u3fvAj1NSEj4piMPh8OZmpoCPUXGHuDLly8XLlwA7pf+/n4NDQ1GRsYtW7ZISUkVFRWBNNPT09nZ2cgEAGy09evXP3z4cOnqobq6mpWVdf369WvWrJGVlW1paYG/r1OgP8PCwlhYWOjp6bds2UJTvZycnHPnzq1Zs4aDg6OkpAR0flNT05UrV4DdGhwcDA7GxcUZGxsjHlgYhpubm0+ePElPT//LL7+oqKhQT3jgl4CAgLVr10IQdPDgQRqT4pvMzs66uroCPTU3NwcSQCaT8/Ly1q5dS0dHd/jwYWRgg1KIRGJISAgLCwsEQXv37qWWewQ/Pz9eXt7Q0NBdu3ZBEMTCwhIWFgbD8NTUlL+/v4mJCfIAUANmCyYmppUrV+ro6NA0DWFwcFBLS2vLli0rV640NjaenJzs6elJSUnp6ekBCdzd3UG5oqKiyFWxsbFVVVUwDFdXV589e5aenl5cXBxY3/7+/vHx8b29vZ6ensjd7+joUFZWZmBgYGdnr6+vBweDgoJ+++23lStXMjExubm50QxkCoWSlJS0fv36lStXHjx4kHoehWEYi8Xy8vIyMDDcunXr48eP4ODU1JSoqGhGRgb4s6am5uLFiwwMDAwMDEttvh+wPP7T4eFhHR0dxGF04MABUVHR169f0/iMpqenNTQ0LCws7OzsgHOTg4Ojrq6OWlLb29uVlJQQNxYXF5eKiso3p4jv6SkA6CmwT2/evJmZmdnQ0PDu3TtgfXBwcJSVlcFUTwkej4+NjTU2NraysuLn54cg6Ndff01NTf3BNgIMw+/evbO2tvbw8Dh16hQwrGg2shYXF2NjY2VlZT9//tzd3S0oKAjadfHixcrKSjs7OwsLC8ReA9LQ3t6upaVlaGiooKAAQdDatWv9/Pxoggd6enru3LnDwMCwc+dOExOTBw8ebN++XVRU9A/FFIbh5ORkYDrt27cPeNkpFAqJRHr58iWoGxMTE5D4f1NPi4qKmJmZwVJ0fn4+LCxsy5YtEAQxMDCcOHHC0NAQhCWAtTC4BOjpypUrFRQUgDGC3KCenh4nJ6cHDx4Al+7WrVsRw/B7C4jW1lY5OTlpaWlw03l4eCoqKpCyMBiMkpISmAj19PTAs+rv73/w4EEGBoaVK1devnwZNPnmzZtmZmbIagm4R5SUlEA3cnFxIVKLiHtsbOy+ffsgCNq8eTMyX/6Ab+opDMNfvnzZtm0buC8vX76k9tWOjY0pKioeOnQIrPbExMRoDDEYhl+9enX27NnR0VFra2vgcWJjY0tPTyeTyd7e3ioqKoj2UQP0FNxTdXX1b/YtDMPd3d1iYmKgbsAjQSaTsVgsUsmlekomk6empkBXf/r06fTp0/T09Hfv3p2cnOzv779//76bm9vi4uLg4CDysHV0dICHkJOTEzGqPDw8gFXExMQUFxdH82TW19eLiIgAwYUg6NGjR9QhPfPz8+fOnQNuJT4+vmfPngFffF1dHdKBNTU1wB1ET0//4cOHP7x9CP+WnlKbBl1dXS4uLkJCQoiqAs8UsqamUCgtLS3y8vIVFRVYLNbS0hKCoHXr1llbW9OoQGdn58OHD4FHA3Dq1KmkpCSa0n9eT4WFhVVUVISEhI4dO7Z+/Xo5ObmMjAwQ+oPUf2BgQEJCIikpCYvFPn36FHS3kpLS97YRYBhub29XUVHx8PCgUCiOjo5gDrCxsaEWAhwOl5ycrKSkBO5KRkYGsuWirq4uLS399OlT4D0EEAgECwuLR48eDQ0NvX37lpGRkY6O7uTJk4gzF2Tb09MjISFBT0+/YsWKo0ePAp06duxYfHz80ltDQ2pq6tGjR2n0FIbh169fg4qtW7cOmH7/pp6WlJQICAg8e/YM/Dk3N+fq6nrw4EHktgoICFhbW3d1dSFVBXq6du1aAwMDxI0LTkVERFy5cqW5udnCwgKMJVlZ2e95FWEYXlhYCA0NVVZWLisrMzU1Be2ysrKiboWPj8+mTZvA/DowMDA6OvrkyRN5eXkw3vbs2VNbW9vd3X379u2QkBDkqrq6uosXL6anpz948ADUFhEdpNuBAw6CoA0bNizVU8rvIEe+p6etra0CAgLg0dLT00Oe84WFhbi4OHV1dR8fH2BQ79y509fXl6YgV1dXXl5e4J8VFhYG3S4iIlJYWBgcHKyqqvoDPQU9c//+fZpqIzdlbGzM2Nj4l19+AcmW3oulekrd5KqqqrNnz9LR0R0/ftzKykpSUpKbm/vNmzc0mXR3d8vKykIQdOjQofLy8q6ursrKytu3b4O5SllZGQkCQRYlERERQkJCAQEBwHt78uTJ4uJiJEMCgfD8+XNwCtwgcXHx4OBg6rrV1NSAPZ6/QE9JJFJ1dTWYvSsqKqytrc+fPw+egIMHD2ZmZoLEMzMzTk5O165d8/Pz+/z5s42NDWgPDw8PEu2BxWIHBwdnZmbm5uZSUlLU1NSQfVJRUVGaJf/P66mMjIyjoyMQ6LVr1yJxBUioPJFIzM7OFhQUTEpKmpmZefXqFZjZ9u3bV1ZW9j0T1cvL6+bNm2/fvsVgMMHBwaCeR44cAZYvyHlqaur58+cSEhIgIopAILx792737t3AwmJiYvLy8qK2PUdHRy9duvTo0SMYhmtra8EkuWLFivDwcOrtIGCf0tPTb9++3dLSUk1NDQzFs2fP5ubmAsn43o5wamrqkSNHluqpv78/aMKOHTuAyfzv6+m1a9devXoFehiHw4Hm3759G9huAGNjY+AuhH/X0y1btrx48QJ4+pD2Pnz40NraGnQR0DsmJiZ/f/9vthGG4c7Ozrt378bFxcEwnJ2dDXT84sWLwJUB+Pz587Vr1yAI2rRpk7+/v6Ojo6+vb1NT0+PHj8FwNTIysra29vT0RB7RqakpPz8/W1tbLBZbUVEBHqpjx46BLXhEcUJDQ8FGzcmTJ7/p2YT/p7h8T097e3vl5OSA20pVVRXRrM7OTnl5+eTkZBiGX758uWHDBgiCLly4QLMl4Orqys3NDR7g9PR0EELAyMh44cIFAwODp0+fLjVp4Z/QU8D4+LiZmRnY3VVXV/9JPUUyqa6uBpq1b98+JSUlVlbWXbt2Uc9bgPfv31+4cAGCoG3btikqKqqqqgoJCa1bt05QUDAgIABZsCP92dDQ8OjRo7i4OBwOJyEhsXr16lWrVtnb21M/vSMjI56enmBNCdi1a5etrS3id/rL9BSG4cXFRWVl5YSEBOR4TU2NtLQ02PP18/MDB6uqqri4uC5evCgvL//06VN9fX3g+lm/fr2XlxcQi66urqCgoJSUFHAJHo+PjIwUEBBgYGDg4OCg2dL9GT0FD6KWltb09HRcXBwY9uzs7Pn5+WA3A4jOwMCAkZGRmJiYqanpq1evzMzMTp48CUHQqlWrVFVVv/nMEQgEOTk5bm5uMzMzd3d3AwMD8PxBEOTo6Ii8DjA2NmZkZHTz5k3gM4JheHx83N7eHmyeQhAUGBhInWdYWJiQkJCamlp0dHRkZCSQsxUrVsjIyFAPy56entu3bzMwMAgICLS3tzc3N1+/fh1kePbsWWTH+Zsmalpa2lI9xeFwTk5OSA6grJ/UUxMTE7CWpNHTDx8+nDp1CswNAwMDKSkpYC+xv7/fz8/v+vXrwKxmYmIqKysDmTs4OABB9/X1BdMMIk98fHyWlpbx8fFJSUlgZw+CoDt37lCHxCIQicS3b9+uXr3azc0tNTXV0dERWItbt24NCQlBJkiwEb9q1aqVK1dycnKePn0aPHsxMTGbNm2ip6ffu3fv4cOHs7KykJxra2uFhIS8vb2rq6uLi4uvXr0KJoAnT55Qe/FevXoFQRADA4OUlBSNFx5sq1LvK8Df19OOjg7EOjE3NwfPOYFAiIiIOHToUHR0dH19vZOTEzMzMzCoU1JSqLMFeopM2J6enmAuhyCIlZU1NjaWxvMI+LGeEgiE+fl5MpkMJnUwxHR1dZfucHzTf0r9eHBwcKxYsUJQULCxsdHX1/f06dPAxAYxBmCEvn37FvERm5ubi4qKgt7Q1NT85vaGs7Pz+fPn6+vr+/v7HRwcQBjMzZs3waKeRCKNjo5OTU0RicSCggI1NTUuLq7Vq1dDEPTLL79ERkaCvqqurgYi/tfoqbi4+KNHj6iX7YODg2AyBG5yEPAvLCwcGhqal5eXnp5eUlLy6NEj0JITJ040NzfDMNze3v7gwQNTU1PqUsLCwjZt2nT48GEa12RKSgoogp2dfemO9tDQkIyMDKKnGAymt7dXVVUV3AxRUVEkoIxCoRQUFIiLi6upqRkYGGhpab1588bNzW3Pnj0QBO3evbu0tHSpML1//15cXPzGjRsmJib6+vrGxsb3798HjyAPDw+y3zI/Px8dHa2oqAi82iCf0dFRbW1tMHiCg4ORPAcGBm7evCkjI2NkZKSvr29iYqKkpPTrr7+CEZuZmYmEQPX29kpISABHJLB8S0tLgSeBnp7e1NT0ezYRDMPp6enIeh8x1rq7u2VkZID9jkSSdXR0IPv7iYmJP9BTMFGZmZlRn/rw4YOgoODz589hGK6trdXU1EQmFRiGe3p69PX1V61axcDA4O7uDqxRR0dH0OcBAQGICoA5aceOHYcOHTp06NDhw4fZ2NiAgu/bty8gIGDp3ens7JSWlmZlZQXhO4cOHdq/fz+wpAQEBKit8pKSEg4ODiAxysrKwA5tbm4GEwlID6KqYRgmEolRUVF79uy5efMmeFXh8uXLINtTp04BEQTZurm5gcu5uLho1tRtbW1OTk40ryrMzs66ubkt1dOKigpktCO7z+3t7dLS0lxcXJKSksBrdOjQITo6unXr1uno6FBPMG5ubtR6SiAQ7O3tQYV37twZGRn5p/QUUF9fX1hYiMfje3t77969C4aYtbX10hdkfqynKSkpa9asoaOju3PnTn9/P4jU9vb2hmF4eno6NDQUCHROTg4fHx8EQSdPnlxYWGhpaQFRAatXr1ZVVaV5zsE+LRcXV0xMTHR09OPHjw8cOEBHR/fbb7+BgQbeSwwMDAQbcRQKpbKyUlFRERh/MjIywLH219inAAKBYGxszMbG5u3tPTs7i8fjCQ6ASqcAACAASURBVATC4OAgGxvb5s2bk5OTyWTyx48fHzx44O/vPz4+TiQS8Xg8kUh8//49MAMhCPL29sbhcL29vTdu3GBnZy8pKVlYWACRcX5+fuvXrxcQEKDetyGTyVFRUQcOHIAg6MCBA319fWQqKBRKZ2fnjRs3QOZKSkpgi7ympubMmTPg4IMHD7q6ukgkUnt7u62t7YsXL3p7e2dmZqampkDwOfDRQBCkra0NhgSyVBkfH5eVlXVychoaGpqbm8NgMLOzs319fcgKwsXFBagPFov18PC4c+cOTShVfX09qImXlxewkRcXF2NiYkRFRSsqKubm5iYnJ6enp79+/WphYQEeWSUlJcQT19PTAwxSRkZGsOijUCixsbH79+8HZrWxsfHXr18RbxeF6r1yZN0H4k9hGCYSiSkpKZycnCtWrLh48WJjYyO4sL29HXQCMzNzYmIite+M+u67ubmBCAddXV1EcwkEQnBwsJqaGnD4NDQ0AGcx9XsmpaWl+/btY2RkDA8PB9UDerp///7ExESkwqmpqVpaWhEREUNDQ4ODg4ODgwMDA/Ly8sB9fP36dWQkI3WLiYm5cOFCSUnJ+Pj48PDw8PBwQUGBiIgIBEEbN27My8tD6tDX14cENiQkJCD3wtXVFagYdaBSQ0MDmO+Dg4Ozs7MHBwc/ffokLi4O5Ck9PR3J1tPTE9FTav84DMMhISEcHBw0MRvz8/Nubm7Ay2RpaQk0kUgk+vn5IZY4iB6FYTgyMpKPj8/HxycmJiYiIiIhIcHGxua3335bsWLFrl27SktLkWzd3Nx4eHiAPY7cUzk5uRUrVuzYseMHevrkyRNg2WloaNCcBZuoFAplYGAAeS3C2tp66U6Dh4cHMIfFxMRobhC4R6BpkpKS/f39FAolPj4+NzcXhuGamppLly6B3fzW1lYJCQlgpgCL1d7eHuzRMTIyGhkZUTfBw8Pj4sWLDg4OSUlJKSkpcXFxBgYGTExMdHR0t2/fnpubI5FIsbGxcnJy1B7Vnp4eKSkpBgYGERERUCiIl/rL9FRaWhos0zQ1NaOjo/38/KSlpZmZmV+8eDE7O9vb26uhobF9+3ZNTc2Kigow5Kanp9PS0hDNYmVlDQ8Pb2xsBDf72LFjjo6OGRkZ4J0ZJiYmHx8fZN9wamqqpqZGW1sbzLTbtm0D6y9g4ywuLvb09Hh7e4PlJARBvLy8MTExYB85LS0NWHzbtm0zMDDIz89/+vQpWEpQ2xH9/f2amprg8t27d/v5+SGDFovFvn79evv27Q4ODtTPx9zcHKLgZ8+eBYN2eHj41q1be/fujYyMpO40CoWSlpa2f/9+BQUFMA/n5eXx8vJev36dxg+VkZEBJs8tW7Ygtlh1dTWy7QtC/2AYHhwc1NbWBmNy7dq1SkpKiGFFrafh4eHAGb9ly5aoqKjh4eHk5OTz58+vXLlSSEjo06dPSMqsrCxg8+7YsQOJMaDRUwqF0tHRcfbsWQiC2NjYXr9+PTs7SyAQoqOjDx069PjxYzDMWltbr169unPnzsePHzc1NYERnpiYuHv3bj4+PmAUkMlkc3NzoE3+/v6gOCKRqKSkdPfuXZqRHxAQAMbqvn37MjIyQIag5t3d3WZmZkpKStS7utQBYSIiIkCbgPc/IyMDhOM0NjYi6XNzc7ds2cLNzU29m/Tq1SteXt6enh4sFovUx8vLC7npSGgUYp9ycHBQP1fV1dW3b9++e/cutRsXhuGxsbGHDx8CbTIzMwMr2Y8fPwKDY8eOHbm5uaCNDQ0NKioqSkpKQ0NDCwsLWCx2cXGxvb1dXV0dlGhkZIQsvR8/fszNzQ3mA8R3WVBQwM3NvW3btnfv3n1TT4lE4qNHj8Cmn5qaGvWphoaGy5cvGxoawjDc398PlA7YHEujuZGJFok/pX54oqKiwLXi4uJgWQA+WNHa2qqionLr1i3QmdXV1WDDjY2NDYSaTk5OgsAMMNP7+/uDBuJwOBUVlfv3709PT8/MzIBtmNraWrByZ2FhiYmJIRAI8fHxLCws+vr6iLsAh8PZ2tquX7/e3NwcrHRra2uBfbpixQqaQKAfswzrfQKB4O3t7e/vHxwcbGdn9/DhQ21tbQsLi5SUFOCnqKiosLOz09PTc3R0zMnJAZsP4J1lFxcXExMTExMTQ0NDb2/v8vLyoqKi0NDQV69emZubKysry8vLGxgYxMfHU69iWltbX716ZWBgYG5ubmZmZmpqamNj4+7uDpRocnIyPj7eyMhIT08PnDU0NDQ2NgbBZQsLC+BlRyMjIwMDAx0dHTExsWPHjomLi3t7e4N11uDgYEBAgISExPXr1w0MDNTV1WVkZMCLXng8vqSkREZGBqy2XFxcwCth09PTYWFhN2/e5Obm5ubm5uXltbGxSU5ONjc3v3DhAi8vr6ysbExMDHUrwF18+vTp+Ph4Y2OjgoLC8ePHr169amhoCCxELBabl5enr69/6tQpbm7u48ePi4uLx8XF5efn6+jocHFxcXNznzhxQlxcHHgkcnJy5OXleXh4wIcLzpw5Y25ujsyu4Ga5u7vz8/OfO3eOh4eHj49PTk7O2Nj43r17kpKSDg4O1IkfP34MXnnk4+Pj4ODg5uY2Nzf/ZrgiDMOpqaliYmL09PSbNm06derUuXPnBAQEdHR0kPflGhsbwcumZ86cOXXq1NmzZ/n5+bm5uVVVVSsrKwkEQmlpqb6+Phh+4Om3sLCorKx0cHBgYGDYuHGjk5NTe3s7aEVmZiZwH4PEbGxs/v7+4DspJSUl169f37hx486dO62srEZHRykUyvT09Nu3bzk5OaHfuXTpEhJX+OXLl/Pnz1tbW1M7yhsaGq5fv66iogK0aXp62s/Pb8eOHfT09K6urojFWlFRAVyogLt37yYkJERHR4PRCNYKBgYGDg4Oz54909PT4+Li2rx5s4WFBRJID8PwwMCAs7MzsvXKyspqYGBgbGwMYgrB66pA+Do7OzU1NdeuXQtchEhtP336hEjb+vXrnz171t/fD9Z/69ate/78+efPnxGvMQ6HCwoKYmVltba2RoLAEEgk0ocPH5BgAG5ubvDBhOLi4pcvX54+fRp4Y8CHFEDEGARBp06dioiIAO5dCoWCwWCqq6uRTA4fPpyent7W1gbqsLCw0NzcDKIjIAjavHmzs7NzWVnZhw8fgEG9bds28OrB169fHz9+DCbODRs2PHv2DDxRBQUFiJeGhYXF3d29uLjYwsJix44dioqK1Mre3NwMJnsIgk6ePJmUlBQWFrZ161ZGRsa7d+9GR0eXlZU9f/6clZX1yJEjwE03MDDw4sUL4GaBIMje3r6rq+vHcZMIy/O+KbIdNDQ0VFlZWVZWhqxx8Hj80NBQT0/PyMhIf3//8PAwMDOxWGxfX19vb+/o6Ojo6OjIyEhHRwcyr1IolC9fvqSlpeXm5i51BU5MTFRUVHz+/Hl8fHxsbGxwcLC+vr6qqgrYIwsLC01NTRUVFUNDQ2NjY2NjY93d3cXFxYixNj8/PzY2Njo62tjYmJWVlZ6enp+fn5mZWV5eDrR+amqqrKwsMzOzrq5uaGiou7s7MzMTWDREIrGjoyMrKysvLy8tLS0zMxNUb2FhobKyMjc3t7CwsKioKDs7u6ysrLq6OiEhITs7u6CgIDExESzkqRsyODgIPmIEZpe8vLysrKzY2FjQezgcrqGhITk5uaCgoKioqLCwMCkp6ePHj42NjYmJicjBxMREYN81NTVlZGTk5+cXFRUVFRVlZWVlZWVRv8xKoVAyMzP9/f0LCwsLCwsLCgpSU1PBDk99fT21+5tCocTFxXl6egJPd0ZGhp+fX3R09Dc3f0D62trawMBAZ2dnOzs7W1vb0NBQxEUFw/Dk5GReXl5eXl5cXJyLi4utra2tra2npycIzIJhuLm5OTQ01NXV1dvb29PT8+XLl9HR0R0dHSkpKa6urp6enomJiYjfs66u7u3bt76+vkjiwsJCYAi3tLT4+vo6Ozu7uLjExcWBR2JkZAR8HMTb29vb29vNzc3LywtRZwwGA77URT1mZmZmKioqqqqqQLajo6NRUVHgyy9PnjxB+iE7O1tNTc3S0tLb29vV1VVXVzcqKiowMNDY2Nje3t7e3t7GxsbU1NTExMTU1PT+/fs3btzQ0NBAjE1QgcbGRmtrawUFBXl5eXl5eTk5OW1tbUtLSxsbG39/f+r3WYHfTEJC4sGDB7m5ueCWzc7OZmVlmZqagsslJCSsra1rampSU1NVVVXl5OQsLCxycnKo/Zvj4+N+fn7BwcE0ekomkwcHB9+9e/fgwQM5OTl5eXktLS1nZ+fg4OA3b95YWlrevn3bysqqu7t7bGzMzc1NVVUVFKqtre3n5wdseTweX1dXFx4erqWlJSsrCzLx9vZ+//49WHPMzs5GRkbK/460tLSdnV1QUBAoQkxMTENDo7q6mkQihYWFaWpqqqury8vLq6qqPn/+PDs7e25ubnFxMSEhQVdXV0ZGRlpa2tbWNjAwUE1NjYODg4+PD4kbw2AwmZmZhoaG8vLysrKyCgoKfn5+xcXFz54909LSUlRUVFNTk5WVvXr16v3798F+6eTkZHh4uIaGhrS0tKKiopycnKqqamRk5NKJ55ug35P+rwCs93/+I3J/6nNzP14K/eFCiSYK5w8T/6Bu3zuFxWK/uZm2tNxv1oRCoczPzy8uLpJIpOHh4fb2dvB1KwqFMjw83NbWhqya+/r6RkZGent7ETcxiUTq7OxsbGxsbm5ubW0FH+6heZ9qfHz88+fPHR0dXV1dXV1dHR0dTU1NS5fPMAwPDQ01NDR0dHS0t7f39PSAfICDq6mpCVwOvpUFPnvY0tICcvv69Sv10p5CoSwuLo6MjNB8zAV8xODz58/Nzc0gt/b29oaGhrq6urq6usbGxra2NqAsGAymrq6ura0NJGtpaWlubgYGPoFA6O7urqurA99y7Orqam1t/fz5c09PD/gOAB6Pr6qqys7O7uzsBAkaGxtBEU1NTaBp4JuHxcXFhYWF3d3dnZ2dHR0djY2NXV1dyMQ/NjbW0dEBGlhfX19dXZ2Wlubl5YXEY0xNTTU2NjY1NYGCWltbm5ubMRjMzMwMBoNpb29PTEz09PSMjo5GLMKJiYnCwkLwWZ+vX7+2t7dnZmZ++PABCen7Maie/ldAo6d/KGEgJU2y712FZL40MXIJ9S/fvHCpW3bpQZASSU99lnorkrqs733EmubU0ibQnPpmF1Ef//kpYWkzfzLBN9X/Xyv33+QHhf64Sj+eDv9UKT+ZyZ/i3/9qLaqn/xXQCNDPDOOlyb53CY10fu/gN/X0mzq7tMLfTP+9rGjq/z09/WYOP+iNn6neH6b5mXyWJvhT1fgP8PO9+pMX/qmU/2aTf5ztv9mZqJ6ioKCgLA+onqKgoKAsD6ieoqCgoCwPqJ6ioKCgLA+onqKgoKAsD6ieoqCgoCwPqJ6ioKCgLA+onqKgoKAsD6ieoqCgoCwPqJ6ioKCgLA+onqKgoKAsD6ieoqCgoCwPqJ6ioKCgLA+onqKgoKAsD6ieoqCgoCwPqJ6ioKCgLA+onqKgoKAsD6ieoqCgoCwPqJ6ioKCgLA+onqKgoKAsD6ieoqCgoCwPqJ6ioKCgLA+onqKgoKAsD6ieoqCgoCwPqJ6ioKCgLA+onqKgoKAsD6ie/pOgUCgUCgWGYTwe39TUlJqaWlxcjMFgvpd+bm7u06dPycnJFRUVi4uL30s2Pj7e0tLS3t7e19f39evXlpaWlpaW4eHhpeX+PBgMJj8/v6qqamFh4U9d+AMoFMrMzExPT8/SipHJ5PHxceT4+Pj4n63wD5ifnyeTycuVGzUUKv438kf5D4Pq6T8JZOCNjo4+fvz45MmT0tLSnz9//l766urqW7dunThxwtPTc25u7nvJuru74+LirKys7t+/b2xs7Orq6uTk9PjxY09Pz/LycjweD4r+yUqSyeSenh5XV9eTJ0+amZkNDQ39yVZ+FyKRWFNTY2Vl9ezZs7dv37a3tyMVI5FIubm5Qb+Tm5u7jArl6uoaGBg4MzOzXBkuBdXT/xugevoPAwy8sbExJycnTk5Ofn7+Dx8+fC/xp0+fhISEWFhYoqKiCATC95Jhsdiampp79+5BEHT69OmQkBB/f399fX1OTs6zZ8/GxcX9wLZdColEqqqqkpKSgiBIUVFxcHDwTzXwxznX1dWZmpoyMzNDEKSuro7YpBQKpbCw8M6dO0xMTJKSkkVFRctVKIVCkZGR0dDQWMaJAWFmZmZ0dHR+fh7V0/8boHr6zwCPxxOJRPA7sFLHxsbu378vJCRUUlJCnRKHw5FIJPA7mUzOyMi4fPlyTEzM93JG1puvXr2CIEhXV3d2dpZEIhEIhPDw8J07d54+ffrLly9/tsKZmZnMzMwGBgZ/Sot/DKgngUBwcHBYvXo1IyPj06dP5+fnwVkymZyenm5qapqYmLhcJQLa2tqWcVagJioqKjAwkNpTgfKPBtXTvzsEAqGlpSUpKSk9Pb23txfRypmZGW1tbWFh4ffv34Mji4uLnz9/TkhIyMnJGRkZAQeLi4tFRUUjIiImJyenp6dnZmYIBAKFQlnqEPT09IQgyNjYGCmitbX17NmzBw8eLCoqIhKJWCx2dnYWh8MBUZuenp6bmwNCv7CwsLCwgMPhsFgsKGJubo6bm9vFxYVIJGIwmOnp6cXFRcRfgcPhZn+HRCKRyWQCgQByAL9MT09jsdjveS3d3NyYmJjo6Oj279/v4+ODmN61tbVPnjyJjo6GYXh+fh6HwxGJRAqFgsfjZ2Zm5ufnSSQSkUgEpYCCQBNgGCaTyXNzc6BcIpEIUpLJZCKRCNpIIpFwONzCwsLi4uLi4iKJRKJQKKBbkDljcXFxdnYWFATyBPmAVoMSwSkSidTf3y8uLm5kZDQzM0OdBovFgjrAv08hZDIZdDuoAzKz4vF4LBaL5PnN24rynwTV07818/PzUVFRV69evXPnjqCgoKCgYGhoKBj/k5OTmpqaiJ5iMJjXr18LCwtLSkqeP39eRkbm48ePMAyXl5dLS0ubmZmpqKjw8vJycXH5+fkhA5Iad3d3CIIMDAxwOBw4kpKSsnfvXl5e3oaGhs7OTm1t7ePHj3t6eoJsBQUFL1++nJKS8uXLF1tbWwkJCWtra11d3TNnzvj6+mIwGH5+fhcXl+zs7PPnz3NyciorK09PT8Mw3NbWZmxsfPfuXRkZGUFBwcjIyIWFhZKSEn19fUNDQz8/PzMzM05OzitXrlRUVHyzW549e/bgwQMTExNmZuajR4/m5eUBMfr06ZOjo2NOTk5PT4+JiYm5ufn79+8pFEpOTs6FCxcUFBSamprq6up8fX2dnZ3fvXtnbGx869at+Pj4xcXF1NRUDQ2NS5cuaWhoREZG5ufnl5aW9vX1lZaWOjg4REdHd3d3JycnGxkZmZqauri4AIs1JydHWVnZz88PTHv29vYPHjzQ1dWNjo4mEokEAuHTp09+fn5FRUVfv34NCwvT09OLi4ujUChfvnyRlZVlZGTk5eV9/vx5QUEBDMMkEik4ONjIyEhHRycoKGhsbAyGYSKRWFxcbGtrW1paWlxc7OjoCBKPj4+/efPG2Nj44cOHcXFxwB2B+g3+WlA9/ftCJpMjIyMFBARcXFzy8/NTU1OFhYUFBARKS0thGMZgMEBPwZ+BgYGCgoLh4eGVlZWOjo579uyRlpYeGhr68OHDkSNHODk5ra2tPT09OTg4hIWFv7l+9/LygiCIj4/Pzs7OycnJ0tKSi4uLh4cnNjZ2YWEBg8GEhIQwMjKamJjAMDwwMGBgYPDLL7/4+vo2Nzfr6enR0dHx8vKqqKgICAj4+vpOTk4KCgoeOXLE3t7excVFTExs69at6enpZDLZwMBg9+7djx8/jo6OFhQU5OPj6+zsbGxsvHv37u7du4WFhc3NzW/fvr1t2zYDA4P+/v6lVbWzs3v8+HFra+uLFy8gCLpx4wZQt6qqKl9f348fP05PT4eGhv7666+Ojo5YLLa7u/v27dt79uzJzMzMy8tTUlLav38/Pz+/mJiYqKioi4tLcHAwHx+ftbV1ZGSkgYEBLy+vqKios7NzY2Pjq1evmJiYnJycpqena2pqFBQUdu/ebWtrOzU1BcPw27dvL1y44OXl1dDQIC8vr6CgkJiYaGhoKCgomJqaisVi3d3df/vtNxEREUVFRXV19WvXrgkLC+fl5Q0ODr58+XL79u2nT5/28fH59OnT3Nycp6fn7du3g4KCXr9+LSAgYGBgMDIyUl1dLS8vv23bNiEhoZs3b544ccLJyam9vV1HR0dTUzMkJMTCwuLYsWPGxsbfnCZR/pOgevr3pa+vT1xcnImJCdgpMAy7uroyMjLq6+vDMDwzM6OpqSkiIlJeXj4/P6+lpbVv3z4fH5/w8HA7OzsODg5RUdHu7u60tLSNGzeqq6sPDAzAMPz8+XMeHp7Q0NClxQE95eTk1NHRMTU11dHR2bVr1+7duyMiIkCC+fn5EydOvHz5EvxZWFi4a9cusPGdmprKxcWlrKxcV1f36dOn/v5+IpHIz89/8ODB9PR0GIaTk5O3bdvm5eWFx+O1tbXV1dXn5+fn5ubU1NQ2btzY0NBAJBKdnJxYWVk1NDTa29sbGxtv3LghJCQErGwa7OzsjIyMRkZGJiYmNDU1165dq6am1tvb+/nz56CgIHBJb2/vrl27LCwsQDyZq6vrvn37srKy+vr63Nzc1q1bJycnl5+fX11dnZOTIykpycvLW19fD8NwdHT0pk2bTp06VV5ePjk5GRgYuHHjRnt7exiGKRRKTEzMxo0bDQ0NJycnYRh2cXGRk5P7+vVrUVERHx/fu3fvYBiOj48/cuSIg4MDHo8vLi4+c+bMb7/9ZmxsnJub6+/vz83NbWlpOT8/X19fz8bGpqOjMzo6OjMzk5KSwsHB4eHhsbi4uLCwoKGhsWXLFkdHx+bmZisrqzVr1ggICPj4+Lx9+zYrK8vJyWnv3r1hYWE4HK6trU1YWHjdunUhISGopP61oHr69wWYluzs7BMTE+BIQUEBCwuLkJAQDMOzs7NATysrK8fHx9XU1Pj4+Nzc3Nzc3Dw8PAIDA4uKihYXFyMjI3fv3h0fHw9yCAgIOHPmjJub29LiPDw8IAiSk5P79OkTCEcNDQ1lZ2fn4uLKz8+HYZhCofDy8np7e4P0KSkpO3fuDAwMJBKJjY2NSkpKyCkYhjs6Oo4ePaqkpATkLD8/f+fOnX5+fjgcrrGxMTs7OyYmxsHB4fr167t3725paYFh+M2bN/z8/D4+PjAMLywsaGtri4iIlJWVLa2qnZ2dsbExuGpwcFBVVXX9+vWPHz8uKiqKiYkBXoKWlpa9e/c+evQIxDk5ODjs27evsLAQhuG8vDxmZmY/Pz+Q2+DgoLS09Llz50Bka2pq6oEDB6SlpcHZ3NzcgwcPqqioAIO0v7//1q1bnJycnz59mpqa0tPTs7S0hGF4YGAgPT09KysrMjJSQUHh2LFjzs7OMAyTSCRjY2MZGRmwJqiqqrpy5YqGhsbk5GR5efmBAwdsbW1hGB4ZGVFQUNi6dSsIAoNh+P3797/++uvJkyfHx8dzc3OZmZmdnJzAqa6uLhEREUFBQSQUNyoqavXq1efPn/9BVBzKfwBUT/++gBHFxsaG2KcdHR3nz5+/fPkyDMOzs7Pa2tpXrlyprKycmJiQlJS8evUq9eUYDAaDwURFRe3evTssLAxsWfj6+p45cwb4QGkA/lNDQ0PqyCpbW1tkk6qvr+/w4cMBAQHgVFZW1s6dO4OCgvB4fH19vaamJnKKSCTGxcXt2bPHysoKeGOzs7MRPW1qanJ2dtbU1LS0tFRTU2NmZm5uboZh+PXr14jWYzCY+/fvX7ly5ZvRYEBPwVUwDA8MDEhISPz6668qKiru7u7V1dXwEj11dHTct29fQUEBiUQCsQfIpILFYr28vPbv3//q1auSkhIzMzNeXl4vLy+kmQcOHJCVlQUvOBCJxJSUlD179ri7uwcGBhoZGSGxWZ8/fzY3N1dWVr5z5w4/P/+LFy9A5np6eg8ePGhqaoJhuKSkRFhYWEdHZ2pqCujpo0ePYBj+8uULNzf31q1bwSQBw3Bvb++dO3cOHz7c2NiYlJS0Z8+ewMBAcKqyspKLi+v69eu9vb3gSGFhIQsLCzs7+w9e7kD5D4Dq6d+XlpaWa9eu7dixA1hVMAwXFRUdO3ZMUlIShuHFxUUNDY0rV65UV1fPzc3Jycnt3bs3OTl5bm6OQCA0NTUFBAS0trampqbu2bMnOjoa7FT4+/ufO3cO2IAAZAfD29sbgiATExPqPWJTU1MIgoAsAgF99eoVOPX27dvt27e/efMGBJyqqamFhISAU2QyOTU1lYmJCSkoPz9/165dISEhFApFSUnp/Pnzzc3NZDLZ2tqaiYkJKOObN2/OnTvn4eEBw/D09LSWlpaoqCgwNmleInr+/Lm5uXlnZyfShKKiouPHj0MQJCYmBpSrqamJiYnJzs4OTA92dnYsLCylpaUkEiktLW3Pnj3Uk0p1dfX169fv3LljYWEhLS398uVLUBbYy2JhYTE0NESW0mNjY1euXBEREeHj43vx4gUIA6ivr7948aKRkdHY2FhPT4++vj6wT+fn57W1tWVlZWtqamAYLisru3r1qp6eHgaDKSsr279/v52dHQzD3d3dAgICmzZtqqqqAqX09fXduXOHg4Ojo6MD3ERET+vq6jg5OQ8cOABaCrp3//79XFxcYMcP5a8C1dO/LyQSKSgoaMOGDRISEs3NzWNjYzY2NufOnQsLCyOTyV+/fhUWFubh4cnLyyORSL6+vlu3bj1y5MiTJ0+CgoLk5eWfPXs2Ozvr7++/adMmHx8fENYD3gIArj1QCoVCWVxcxGAwwBRVUVEZHBzEYDAjIyNZWVn8/PxMoWbCWgAAIABJREFUTEyvX7+mUCjd3d3Hjh27ePFiVVVVS0uLoqIiIyPj48ePx8bGAgMDz58/7+HhAcQLh8OFh4dv2bLFxMQExMPGxcVt3LjRxcVlbm5OVFSUjY3t/fv3jY2NEhISGzZsiI+Pn5+f9/Dw4OLievHiBYVCAevfCxcuFBYWgjAg5N/5+Xlzc3NNTc3q6mqkFUQi0cfHZ/PmzRcvXgQq09LSwszMrK+v39PTMzg4KCMjs2fPnsTERCwW6+fnt379+hcvXgCbnUAgpKWlXblyJSEhoa2trbW1tb+/HwQhkUikpKQkZmbmmzdvdnd3g7JwOFxAQAATE9OWLVuioqJgGMZisa6urps3bw4MDMRgMHFxcSIiIpaWllNTU2NjYzdu3Lh27Rrw6hYWFgoICKiqqo6Ojn748IGFhcXExGRycrKjo8PExGTr1q1Pnz4FL8smJSWxsrLeuXNneno6KSlpx44d3t7eQOX7+vrk5OQ2btyYkJCAx+NJJFJISAgzM7OysjISjYvyl4Dq6d+aoaEhKyurQ4cOiYqKCgkJgb1gLBY7MTHx5MmTzZs3r1mzxszMbGpqCmy4b9u2bdOmTTt37tTU1Ozt7S0pKTl+/Dg9Pb2AgEBBQUFOTo6goOCaNWuEhYWBuQQoLS01MzPj4OCAIIiZmVlXV9fY2PjMmTOcnJwSEhIhISFgFYnH442MjLZv387CwiIrK3v//v1ffvlFWFg4OjoahP5cvnwZLM+7urrk5eUZGBhYWFiys7OHhoaUlJTo6el5eXmzsrLk5eVXrVrFwsLCz88vIiKyatUqLi6ukJAQaWnp1atXa2trT01NFRUV8fDw7Nixw8PDA4vFwr/b0Xg8PiAggJWVdf/+/Q8ePKB+l2Fubk5LS0tKSqqhoQGG4YGBAUFBwa1bt16+fFlRUfHw4cMMDAzCwsL19fWqqqorVqy4e/cusIsXFhbevHmzc+dONjY2Li6u48ePnzlzxsDAoLKycm5uzsbGhpGRkYeHB1klwDA8MTFx9OhRKSkp4ATA4/Fv377dsGHD4cOHJSUlT5w4sWbNmm3btqmpqWVkZLCzs+/duzcuLg6G4dDQ0G3btp06daq4uLi+vv706dMHDhy4dOmSlZVVU1OTuLj4kSNH3NzcqqqqZGVlWVlZ09PTsVisg4PD2rVrNTU1EZ9Deno6Ozv7rVu3wsPDMzMzRUVFOTg4SkpK0PjTvxZUT//ujI6OFhcX5+TkpKenFxcXg23lxcXF2trazMzM9PT0uro64KMcGBgoLCxMTk5OSEgA2xqDg4OZmZlZWVn5+fmDg4P9/f3FxcUZGRklJSXU7+QMDw9XVFRkZ2dnZ2dnZmZ++PChvLw8KSkpLS2tsbGR+oMmPT09b968sbe3z8rKqqqq8vHxKSws7Orq+vjxY3p6enR0dHl5OQzDs7OzFRUVWVlZvr6+FRUV8/PzlZWVWVlZubm5fX19jY2NL1++fPLkCaiJl5dXbGxsTk5OVFQU+H1gYKC6uvrp06fGxsZpaWlgjwV5ESAkJMTIyMjExMTFxYVm97+hoSE7OxtEMgAHhamp6aNHj9LS0kJCQhwcHHJycpqamtzd3Y2Nje3s7ICndXp62s3NTUBAQFZWVklJ6cyZM/v27ePk5Hz69Onk5GRYWJixsfGTJ09yc3OR3Z7p6elz584hHgMKhTI4OOjm5nb9+nUTExMQ2SotLR0VFZWTk2NjY3P//v2IiIjW1tb4+HgTE5MnT54UFBRMTk76+vry8fHdu3cPBBE3NDQYGBjcu3dPXl5eS0sLBMZOTk7ev3//woULcnJyxcXFoMT5+fmEhAQ1NTVpaWkpKSkVFZX4+Hh0c/8vB9VTlD8HeDkK/L50AE9NTVGHlJPJZGBd0oDH45F3ikAmWCwWh8ORyeTZ2dm5ubm5ubnh4eHBwcHp6WnwQheASCQODg4ODQ2NjIwMDQ3NzMzQfJwJvM6EfHRqYmICzEDg9ScYhkHOIyMjPT094FR+fv7Vq1cTExMxGMzs7GxnZ2dsbKycnJyRkREGgxkfHx8eHh4YGBgaGsJgMOAlsYCAABkZGZrYAywW29DQAAJmR0dHOzo6wFevhoeHOzo6uru7Qc2Hh4eHhoZGR0cpFMrExMT79++RjTUYhvv6+nJzc+Pi4pDP3CwsLLx//76srKy0tPTr16/U7W1oaMjIyEhISGhoaEAcvn/yfqIsJ6ieovwrION26bfmlr71SCaTkSPUZ6kP/rgsav/pN8/SHKQu8ZvVpiY0NJSOjk5VVTU6OjojIyMuLs7Ozk5TUzMtLQ15VQxQWVmppKQkLy9/5MiRoKAg6s2ff0HIqC/5QeuWHvle6753HOU/BqqnKH8OyrdYenZp4h9c/oM8/2zipdX4w6vq6+uVlZUPHTp0+/bt+/fvS0tL37t3z9fXF9nbQRKD2Ck2NjZFRUWaF7doiqM5+Iddt/TI0s5cmsM378ufuJcoyw2qpygoMIlE+vDhQ05OTl5e3ocPH0ZHR7+ZbHR0NDs7u6ysDPncyX+2mih/d1A9RUH5/4AAqR+o5FJr8T9SL5R/DKieoqB820354/To4hplKaieoqCgoCwPqJ6ioKCgLA+onv5pyGRyR0eHr6+vtbW1tbW1g4NDSEiIt7e3ubm5iYlJaWlpRUWFh4cHOPvs2TMfHx9bW1t7e/uUlBSaz1WAz8E9e/bM1dX16dOnYWFhCQkJICgSoaury8PDw9PT08HBwcjIKCIiAmQCvh1laWlpampqY2Pzze8wIeDx+MzMzCdPniCvh/8vMTY2Fhoa6uLiAt4XWLrz/meZnJzMysoKCAiIjY399OkT9an+/v7ExMTw8PDY2NjQ0NBPnz4t4/+tshQMBpOXl5eZmUn9vZiZmZnPnz9/+vSpp6enp6fny5cv4O4QicTh4eG2travX792dnaOjo7+bwfbgw/WFBcXl5aWgk/A/Gt9jkQpLHP9/jtA9fRPQyKRmpqa7O3tGRkZIQgSERFxdXW1s7OTlpY+ePCgsrJyUFCQubn5tm3bIAi6du2anZ2dtra2uLi4oKCgnZ0dEmczMzPj6up669YtfX19KysrKSmpc+fO3bhxo62tjbq4lpYWCwsL8DLowYMHfXx8wOf75ufnvby8WFhYNm/efP369dzc3B/UeXFx8c2bN6Kiomlpaf97PQNqq6CgICYmhnz6aGBgoKOj418en2NjY9HR0QoKCry8vLdv36Z+Iaq7u9vX1/f27dtcXFwGBgYlJSXL+H9TL6WtrU1PT09bW5u6lLGxsfj4eCMjI2VlZXV19aCgIBAbsLi4WFFR8fTpUwUFBWNj47Kysh/8f4jLQm9vr7n5/2PvPMOayta+zzPqjCOOXZAiIkVFigoKKKC0gCBSBKQTUEC6WEAQRboUKVKliYiCKB2UJopIR3rvLUDoEEISSNnvh3XNvnKhM2fOjHPO886zf5+SXdZaWdn7v+51r3I7ycjIODs7gxViiCb+50H09N+DRjd7HIVC7dixIyMjAz5bXFzs4ODQ0NCAx+P19PTY2dnBbsoQBA0PD6upqf38888+Pj4QBFGp1Ly8vFOnTsF73E1MTFy7dk1LS4teT2m/xhQyMjLasGHDkydP6I9DEHT//n14L7jfZ2VlZWxs7G8NegxBEFjwU1dXB5uKCQkJwcHBfzHZT58+nT17loGBQUVFBd4hFIIgIpEYHBzMyspaU1PzF7P4l4yPj6empr5584ZeGVdXV7u7u11dXRkYGBgYGOCHgUKhNDY26ujo/PLLLxYWFmCn6r+V3t5eXV3dn3/++d69e/CGuX8CGo02MDAwPDz8txr7/1QQPf33oB/VlZeX37lzJ7xVM4VCIRAI7e3tYHMmXV3dAwcOFBQUwPc+efIE2LMQBJHJ5IcPHwoKCsbExACBptFoxcXFVlZW9OII8iISifb29nv27Hn69Cn9cTKZfPfuXRcXl4GBAejXJZXLy8tkMnlubg6DweBwOPj6lZUVHA4HYudhsVgsFjs9PT0zMwPi5Y2Pj4Nd4sH1c3NzIyMjExMTcC8VREOCIAjE2gMTMEkk0vj4+OTkJH3sPLDjEQRBBAKhsbHR2Nj41q1bKysr4AIymYzFYjEYDLDy4MpcWVmZnJycn59fW1v7eqXQ9PS0s7Pzxo0bN2zY4OzsDLYFAXz8+JGLi6u9vR0+AoL9wUub4KRWV1dxONw3ZQKPx8M/6mvoZ1CBxa9wyuBzR0eHhITE5s2bnz9/DidSX1+vra198+ZNONA0mUymz53+WaJQKL+zNdRvWZrrSvL582dmZmZ/f/+/sqv08PAwGo2OjIz8ra3/kIkNvwOip38eOTm57du3v3jxgkKhTE1NZWVlVVZWguXqo6Oj2travLy8lZWVYBUgmUwOCQlhZGQ0MjKCIIhGo2VnZ/Py8vLw8MAB7ufn558+fQpvug6zsrJy/fp1JiYmWE8Ba2trzs7OLi4uQ0NDZDK5srIyKCgoPDy8qKjI3d1dVVU1IiICh8PRaLSurq6YmJigoKDBwcHe3l43Nzc9Pb2rV6+CRZPv3r27cuWKra0t2Ie/t7c3KCjI1tbW2to6Ly9vbW0Nh8N9+PAhIyNjfHz87du3AQEBDQ0NRCKxoKDAzs7u1q1bUVFR/f39wLOcnp7+5csXEonU0NBw+fJlNjY2ExOTjx8/zszMrKysFBcX375928zM7Pnz52BjOgiCCARCVlbW/fv3AwICSkpKwNp2+l+KxWL9/PzExMQEBQV37Njh5+cHq095eTkXFxccEWtoaOjdu3fp6enZ2dnd3d1we4DBYAoLC1+/fp2VlYXFYpeWlpaXl4E0jI+PZ2Zmpqenw1mvrKyAQKeLi4uVlZWFhYWjo6MLCwtNTU3t7e1fe0JBW3j06FFhYWGwI8zi4qKnp6eKigocaBqLxZaUlKSlpYHKgX5VQyqVOjc3V11dnZub293dvbKyAqKuLi0tLS4urqysgNCnZDIZHFxdXaVSqQQCYXZ2tqamZmRkBC5PXV0dCwtLQEAAHo+nUCg4HG5ubg4ETwV6jcPhlpaWwFkQKnV5eRnEpgWnZmZmwsPD9+3bFxUVBZ4cGo2Gx+NBhFoCgQCOfHNpLAKE6OlfAYVCbdq0ycXFpbq6+smTJ9LS0k+ePAHv+ejoqI6ODjc3d3p6+sePH0tKSoKCgvj4+ERERIqKisDtOBzOzs5u8+bNrKyspqamYDs4HA4H7+kJA/T08OHDIBIyDNBTZ2dnLBYLAi7t2bOHj4/v/Pnz6urqR44ckZSULCoqmp+f9/T0PHHihJycHNjtKSIigomJiZOTs7GxEYyc6OvrKyoqDgwMDA0NXbp0ycHBoaSk5OrVq0eOHAkODi4pKVFRUTl48KCxsfH58+eZmZnv3LmTm5uLRqMDAwN9fHyOHDmSkJAwNjZmYGBw4MCBGzduzM/P9/b26uvrs7OzGxgYfPjwobOz09XVVVRU1MHBwdnZWVxc/M6dOxAE4fF4MJQXHx9vZGSkpqZWWVm57nXFYDAPHz60trZOT08XEhJiYmJKTk4Gp8rKymD7dGBgwMbGxtjYOCIiQl5eXkFBAfhbx8fHHR0dtbS0YmJiTExMhIWFhYSE7t27t7y83NbW5uDgcO/ePV9fX1FRUXt7+7a2tsePHwsJCUlKSlpaWgoJCfHw8Li7u9vZ2fHx8fn6+n79B4E/zsXFhZGR0dzcHIfDvXz5UkVFBY7P2tbWZm5uLi8vf/HiRUlJSR8fH7g9KCws1NPTs7CwuHfvnpKSkrW19Z07d5ydnUFUFUtLS2CMNzY2ampqKisrl5WV1dbWotHoy5cvq6qqnjt3LikpCSRVXV29b9++R48eUSiU/Px8GRkZISEhZ2fnpqamkpISQ0NDY2NjHR0dHR2dwsJCPB7//PlzdXX1q1ev3r9/X0VFRVZW9vr162fPnt20aZOkpOTDhw8nJiZqamp0dHQ0NTVRKJStrW1fXx+EmKi/DaKnfx4UCvU///M/1tbWaWlp165dY2NjCw4OBl1ssOPvvn37bty4ce3aNTQaLSUlxcDAoKqqSj98PzQ09PDhw7179zIwMAgKCvr6+sI9dHrweDx40Om9BxCdfToyMjIzMxMdHS0oKCgpKZmUlFRVVeXj4yMhIREUFEQkEj9//nzhwgUJCQmg2mNjY4aGhiwsLGCL+/b2dktLy6CgIBwOFxUVxc7Orqam5uPjo66uzsDAcOrUqTdv3tjZ2f34449gl5C0tDQwW0BDQ2NiYmJmZgaNRiclJeFwuIiIiCNHjujp6U1PT5NIJH9/fxEREbDxXUdHBzMzMx8fX1VVVW9vr7i4+NmzZyEImpmZOXz4MChnaWmpu7t7fn7+uq43BoPx8fG5ffv24uJiaWkpKyvrwYMHc3NzIQiqq6uTk5MDHg8XF5cTJ048fPgwLS1NX1+fgYFBT09vYmIiKSmJn5//7t27w8PDz58//+mnn8TFxUtKSoaGhtzc3BQUFGJjY58/fy4vL79t2zZ/f/+PHz9KSEhs3LjRwcHBzc3t7t27ZWVlAQEBHBwcDg4O6zZJAdBotN7eXgkJCXZ2djc3N1dXVzjc09DQkLa2tpGRUX5+/vv37+3s7NjZ2SMiIpaXl8fHxzU0NMTFxcvLyz99+iQmJrZ161Zra+tPnz75+Pjs2rULDgnV0tLCz8+vo6MzNDR09+5d0KIUFxefPn1aXl6+sbERgqD6+no+Pr6wsDAikWhnZ8fFxXX//v1Pnz41NTWdPn36wIED0dHRcXFxhw8fNjQ0JJFIr1+/Pnbs2A8//KClpWVgYKCvr5+WlmZnZ7dz504fH5/q6urPnz8rKiry8vLm5OSEhYVxc3N7eXkBPwCip98E0dM/j7y8/JYtW0JDQ0FECnt7+9TUVFhPwXD/ixcvsrOz09PTwRt+5MgRf39/+gHi5eXl7OxsCwuLTZs2bd682cbGBo4WBQP0VFBQEPbVAmA9BVbD8PDw5cuXjY2NQeS4lpYWc3NzT09PCIJoNJqDg4O8vDy8KXJ2dvb+/fujo6NXV1cDAwNv3bo1Pj4+ODioq6t7/Phxa2trFxcXR0dHfX19d3f3vr6+uLg4sL89uJ1Go/n5+QFDtbKysr+/HxS7o6NDTU3N1NQUfH3y5ImEhASIfLe0tBQXF1dYWPjp0ycvLy92dnYQCGtpaQls4RwdHT00NDQ3Nzc+Pr5u0ScGg/H29ra3twdVFxQUxMjIePLkydbW1qGhISsrq9HR0bGxMTExMXZ2dkdHR3t7exMTExQKBfZgtrGxYWNjKykpgSBodnaWl5cXxIitqqpSVFQEkZlv3LgBAlZ7eXktLCw4OjpycXE1NDQQCARgS5aUlMjJyTk5OX1TT+FaPXToENAj0NMnkUjBwcEbNmyAw1U1Nzfz8vLy8fGBoIeHDx82MDAAVerj4/PTTz8Brw4ej7ewsODn5+/q6iKTyWAfbjA9IyYm5u7duxAELS4uXrx4kZOTMyUlBYKgtra28+fP+/v7+/j4GBkZPXv2DDRLY2Nj0tLSrq6uq6urnZ2dAgICkpKSNBptcnLSxMSEk5MzKiqqu7u7v7+fRCLFxMSwsLAAu76xsVFfXx88Qo2NjSwsLMbGxvTOa4R1IHr655GTk9uxYwfYdx2CoN7eXvBEQr+Gej516hT9+EN9ff2hQ4d4eHg6OzuBzdjd3Q1OLSws+Pn5HT16lJGRMScnZ52arKys2NjYbN68GQ7JCaBQKG5ubnfu3AFD3u3t7erq6np6esADW1tba25uDqYT4PF4a2trOTk5WE/b2trOnDmjpKQEuuEgNOmXL1/Onz+vpaVVUVHR29vb0dHR09MDJCw8PJyZmRnezxhkh0Kh9uzZIyAg8PDhQzBHp66uTklJydTUFMw/jYiIOH36NBzbjkgkvnjxwsvLy9ramo2NDYVCgeNpaWnHjh1jYmLS19fPzc39eiQE1lMwYjY7O2tra7thwwY0Gp2dnX3z5k0MBlNdXX3kyBEUCpWYmBgeHp6QkFBZWTkwMECj0by8vA4cOBATEwNBUGtr6/79+11dXclkcmJioqCgoLm5eWRkZFRUVExMzLNnz9rb27FYrKWlJR8fH2iZADk5OWfPnnVycvpmfx+etqmoqMjAwADHesLhcCYmJgwMDHFxceDI8PCwkpLSpk2bqqqqZmZmhIWFlZSUgA/08ePHbGxsb9++BVe+ePGCnZ3d19eXSCS6ubm5u7uDoa2lpaWSkpKIiIjg4GBZWVleXl4gwW1tbWJiYsrKyr/88gt9HDACgfDhw4e0tLSIiAg3N7fDhw+DloxCoTg4OCgqKsJhDggEQmhoKDMzc2lpKfTrtuVPnz5NSkry9vZmYmIC0a2//vkIAERP/zwKCgrr5kvBTE1NXb58+eTJk/TzkyYnJ0F45KKiopmZGSsrq5CQEPoOflBQ0C+//BIeHr5uxINIJN65c4eBgWFdnGcKhWJoaOjq6gpMhu7ubtBxGx0dhSAoLS1NUVExMDAQgiACgWBjYyMvLw8L4vT0tIuLCwsLi7W1dWhoKOgwNjc3nz9/XlFREd7hmEqljoyMDAwMhIWF7du3D5Zj4LFtamoKCgqSk5PbuHGju7s7iUT68uXLhQsXrly5AuuphIQEEDI8Hn/v3j1ZWdmMjAwsFqupqQkCX8/Pzy8sLLx//97e3p6Li+vEiROpqalf+099fX0dHBxgqW1padHQ0Ni9e7eMjIylpeX09HRLSwsvL6+FhQX9jWDP6Y6ODnV1dRQKVVZW9vDhQzQaDeKyhIaGsrGxgSYHZmlpaXBw0Nra+vDhw/S2WHZ29rlz55ydnb+pp7B4KSkpbd++HRiMEAThcLgrV64wMDBERUWBIwMDA0pKSjt27KitraVQKNbW1idPngwLC4uPj7ewsLCwsIAnePT19aHRaDExsby8PDMzs5cvX4IEKyoqbt++rampGRcXZ2trq6KiAiS4rq5uz549kpKSHBwcly9fhltrEon04cOHBw8eWFhYeHp6njlzRkZGBoKg1dVVOzs7WVlZYLlDELSysgL0FIxMEgiE3NxcAwMDBweHhIQETk7Oa9eufd1/QoBB9PTfA3ji19bWZmdnxcXFN23aFBUVtW4KDpFIrKurk5WV3b9/f0FBweLi4tLS0tDQ0NOnTwUEBMTExEDodisrK01NzZKSkuXl5ZWVlYGBAScnJw4ODuAWpAfEs2NmZtbX14fHcxcXF9+/fy8kJAQP+tfV1cnLy1+6dAk4E2NjY/n5+e/fvw8uvnr1qqSkJDztn0KhFBUV7dy5k950GhsbMzc337hxo42NDehKp6amBgYGlpWVBQcHMzExgdcMgqDc3FxDQ0NgxSwvLwsLC8vJyS0sLLS0tMjJyRkYGAA3cWho6LFjx7y8vJaWlpqamvbu3QsCW9XV1Z06dUpUVHRoaKi+vt7Lywso+PPnz0+ePOnk5ATP8QTCOjk5+eDBA2tra/q+dk1Njbi4OAMDAxqNnpubw2KxMjIyBw4cePXq1dLS0uzsbElJSXR09ODg4NLSkouLi6Cg4NWrV2/fvg1vfV9YWMjPzy8sLPzp0ycw4p+SkvL69euOjg5ra2s+Pj56S/nt27fAPv39napVVFS2b98Oe2bweDxoC52dncGRwcFBaWlpfn7+1tZWCoUSGRkpLS0tKysrKSkZERFBH4cGZLpt27bjx4/fvHkT6GNtba20tPTp06eHhoYgCHJ0dLx27VpTUxMEQfX19RwcHCEhIcHBwYcPH0aj0cDnMD4+LiMj4+DgAGITyMjInDt3DoIgMpl848YN0MyA7AgEQnBwMDMzM5ilUFZWJisrq6mpSaFQsFgsHx+fpaXl1NQUMr7/WyB6+m9DpVLHxsbAEAcjI6OJiUlDQwP9O9ba2urk5MTJyXngwAFXV9fMzMycnBwbG5uDBw+KiIgkJSWBSaA3btxgYmLS09NLSUl58eLF7du3T506ZW9vDzrO65iYmDAwMNi7dy8ajf7w4UNra2tCQoK2tvatW7eA8xSMBe3fv//MmTMVFRUkEik0NHTv3r36+vrj4+MdHR0XL148dOhQbGwsLEkTExMqKiqCgoKw1UmlUouLi5mZmbdu3aqgoKChoYFCoeLj4ycmJpydnXft2pWQkAAaj9LSUhQKZWlpCWRXUlLyypUrJBKppKREQEBAXl4eRPtITEzk4+M7e/bsmzdvMjMzmZiY+Pj4PDw8zMzMtm7dumvXrocPHw4MDCgqKnp7e09PT5eUlNja2oaHh9PrKYlEqqmpMTY2VldX7+npgY13Go0WHx/PyclpamoK4qz4+/szMjLy8vLevXvX0dHx3LlzycnJFAolOztbTEwMhUI9evQoNDQ0Pj6+qqqKSCROTEzY2Nj89NNPR48edXV1ffTokaysbHx8/MDAgIKCAjs7O5gdBaYrpaamHjlyRFNT8+vpXKDqCATC9PS0pKTkTz/9FBkZCcaRqFRqdXX18ePHpaSkQPiv/Px8Pj4+Ozs7LBa7vLx86dKlo0ePxsfHl5WVDQwMTE1NrayswAPofX194uLijIyMr169As9YeXn5iRMnQPS9+vp6UVFRPj6+qKgoMB9r9+7dDx486OvrMzMzY2BgMDY2npmZaW5uZmVlvXz5ck9PT1FREQ8Pz7Fjx4aGhqanp69cuSIqKpqdnQ1qlUgkRkRE7N69Oz09fWxsDEyRRqPRGAzm2bNnu3fvNjAwqK+v/yvzW//ZIHr6b0OhUIaHh1+/fh0aGhoaGhoVFVVcXEy/IqWmpiYyMjIkJCQ8PDwxMTE1NRVEmsvJyenv7weDG2trax8/fnz8+HFAQMDt27eNjY1dXFxAR/i3Wv7JycmEhAQTExMTExMwXvTy5UsMBgNes76+vnv37ikoKGhpaeXl5VVWVkZFRTk5OT148CAtLa20tNTU1BSFQjk6OsLWGZFILC4uzsjIAL1akC8ej39R7qpbAAAgAElEQVT16tXVq1eVlZXV1NQSExPn5uZKSkqMjIxQKJSRkRHoGw4PD3t5eWlpaZmbm1tbWz948KCjo2NoaMjDw0NZWVlTUzMqKmp2dnZhYcHb21tBQSE8PLy+vt7e3l5JSenKlSv+/v52dnZaWlrZ2dnAVJeRkREWFhYVFQ0PD19YWKCvhM+fP1+9ehWFQoH5RqD9AGCx2KdPn4aGhgJHJ5j2v3Pnzu3bt584ccLPzw84+5KTk7m4uHbu3HngwAEODg5WVlY+Pr4XL15QqdTm5mZjY+Pdu3dv375dREQkOjp6dHT04cOHW7du/fHHHxUUFIAzemhoyMzM7KeffmJlZQ0ODv46KNbq6mpBQYGGhsbWrVs3bNggKCiYmJgITpHJ5JycnJMnT54+fdrY2FhMTMzIyGhgYIBKpRKJRCMjo82bN/Pw8AgKCgoICPDx8d25cwderQtiBaqpqQELFIKgsbExe3v7zZs3Hzx40MDAQE5OjpGRUUtLKz8/39bW9scff+Tn58/JyQkNDWViYvr555/19fVDQ0MlJCR2797Nw8OjrKx8/PhxRkZGa2vrFy9eHD16dNu2bZaWlmACL41G+/TpEzMzMzs7+9WrVz09PaWlpXft2iUoKHju3DlGRsYdO3a4ubmt24YCAQbR038bGo1GJBKBWCwvL8/Ozs7MzND3QxcXF8FaIzBBGovFTk5OruvHAbMLj8dPTU21t7fX19cPDQ391vocmLW1te7u7pqamtraWjD3Gz6Fw+F6enra2tra29unpqawWOzY2BgWix0dHQWWSFdXV0tLS0dHBzxhi0ajra6ugih49LmQyeSxsbG2tra2tjYgHOPj483NzW1tbXV1dcB8JpPJExMTzc3N1dXV1dXVoF+Jw+E6OjpaW1tbW1t7enqAJTs9Pd3c3Dw8PEwgEMbGxtrb29va2kA0vb6+PhwOR6FQ+vr6Pn/+nJmZmZ+f/3UckcnJyaqqqtra2rq6uuLi4nWjVXg8fnJyErZnsVhsaWlpTk7Ox48fQSNHoVAsLCwuXrxYVFSUk5OTm5ubm5srLy9vbW09Pj5Oo9GGh4c/fvyYnZ1dWloK/N3Nzc35+fkFBQWFhYVgWjsOh6urqysoKCgqKvrmlH4KhTIyMlJcXPzu3buioqKCgoLu7m7YzAQm9tOnTxMTEwsLC+Els2CBcnBwcFJSkvWv8PDwJCQkgAswGIyLi0tQUBA8CkShUNra2h49ehQZGfnp06fy8vKwsLDMzEwMBlNfX19YWFhUVDQyMjI2NlZRUZGfn19aWtrd3V1XV/fgwQN3d/f379/n5eVFRkaCWRmlpaUFBQUZGRnwgojFxcWoqCgbG5vXr18PDg6WlJR4enr6+/sXFRXFxMSEh4fX1tYCm/33n9X/myB6ivC/Dvrp4v/We/vNi/v6+o4fP37u3DnYquro6JCSknJzc6Mfvv+dRP5IXJNvZk39FfjIurEsNBp9/PhxsOkXaN7y8vJkZGQiIiKam5uLi4sjIyPFxMSqq6vXSRh9OvAC399ncXERbvXX/SKwQhf+ChwX8DV4PB60HxQK5a9vGPbPBtFThP8+QHTo1zKuW5m+jt9Kh/4aWA76+vrMzc3Z2NikpaWvXr165cqVa9eu2drawj1o+EYqHfBX+uO/U4BvlnPdjfRXgs/W1tYMDAxnz569c+eOq6srWCcGFsVqa2sfOnQI7EkGeglf50t/hL4C6Yu6rszfrNjfqU/69OGDyHjUb4HoKcJ/n28KKPyV/sO/fI3he+ErSSRSY2Ojq6urkpISCoVSVlYOCwuD9yhZdyN97r8lSb+T9W8l+PVXQF1d3c2bN6WlpYWEhM6cOaOoqBgWFkYgEDo6OtBotISEhIeHxzf3SflmCb+uvW/+tN/iO1bF/1kQPUX4J0OjM1S/PvW/RBcWFxe7u7vXDfJMTU2BecQI/x+B6CnCP5n/L/R0Hf87S4XwR0D0FAEBAeH7gOgpAgICwvcB0VMEBASE7wOipwgICAjfB0RPERAQEL4PiJ4iICAgfB8QPUVAQED4PiB6ioCAgPB9QPQUAQEB4fuA6CkCAgLC9wHRUwQEBITvA6KnCAgICN8HRE8REBAQvg+IniIgICB8HxA9RUBAQPg+IHqKgICA8H1A9BQBAQHh+4DoKQICAsL3AdFTBAQEhO8DoqcI/x3WxRzG4/EDAwMzMzP/xSIhIPxFED1F+I+Cx+OHh4fn5uZgPaXRaGNjY+Hh4TY2NiUlJf/tAiIg/HkQPUX4z0GlUvPz83V1dV+9egUfJJPJb9684ePj4+TkfP36NTj4W6HewVcCgbC0tLS6uvr1Zd+8fh3w9aurq4uLiysrK0hYeYTvAqKnCP85iETilStXNmzYcOfOHfggjUZbXFy8fv26iIhIamoq/XE41DOVSoU/02i0Z8+eBQUF9fX1/VZG65wJ9GnSf3j//r2Xl1dtbS34+lt3ISD8QRA9RfjP0dzcfOjQIQYGBlVV1c7OTvpTPj4+UlJSmZmZi4uLDQ0N9KeGhobevn376dOnoaEhMplcV1cnKiqqqanZ399Pf9ng4OD8/DwEQXg8vra2tqqqCpZgAIFAaG1t7enpAaK5tLRkZmYmLy+PwWDABYiYIvxFED1F+A8xMzPj5OR0/fp1DQ0NLi6usLAw+BSNRvPy8hIQEEChUOfPnxcSEnJycsJisRAElZSU3LhxA41Gq6urOzg4TE5O3rx5k4GBgZOT083Nzc/PT1dX18DAwMHB4ezZs7a2thkZGUFBQXp6eoaGhg4ODrBq5+fno9FoU1NTVVXVgICA2dnZ9PR0Jiam3bt3Ozk5vX37lkQi/XfqBeEfBKKnCP8hOjs7VVVVW1paOjs7jx8/fvnyZQKBAJ/19vbm4eGRl5d3dXW9cOHCnj17YmJiCASCqampmppaSUmJq6srCoWanJzMyspiZ2dXVlZ+9erVixcv1NTUGBgYpKWlzczMIiIiLl++fPTo0cjIyMjISCYmpvDwcAqF0tbWZmZmZmxsHBkZKSUlxcbGVl1d/f79+/379x85ciQ2NraqqgrRU4S/DqKnCP8JSCRSUlKSqKhoZGRkUVHR8ePHeXl5P3/+DF/g6el5/Pjx2NhYCIK6uroUFRW1tLRGRkb09fVFREQ+fvzY1dVVXFxMJpMhCJKVlfX19QU3lpeXMzMze3p6Li0tQRD0/PnzgICAkZGRhISEbdu23b17l0KheHp6qqurDw8PQxD04cMHV1fXzs7OyclJaWnpS5cugXSQ8SiEvw6ipwj/Cdrb2y9evHj69GkdHZ1r166Jiopu3779xo0bRCIRgiAajebh4SEhIZGSkgJBEA6HCwkJkZOTa29vz8vLO3v2rKCgoLOzc1dXFwRBCwsLIiIi3t7eIOXKykoWFpagoCBg7eLx+Pr6+qioKDQafejQocDAQCqVampqKicnt7y8TF+krq4uSUlJVVVV8BUMeSGSivBXQPQU4W8EnmH66tUreXn55OTkkpKSgoKCFy9eSEpK8vHx1dbWgivd3d0lJSXT0tIgCFpZWXn8+PH58+dra2sJBEJLS4ulpSUbG5ukpGR/f//79+8PHDjg4+MDbqytrWVhYQkODgYd9qSkJHl5+bi4uJaWFtDBp9FoVlZWhw4dqqmpAbfMzc0tLCy0tbVJSEhoaGjARUX0FOEvgugpwt8IjUajUCiNjY3Ozs7+/v5zc3MUCmVtbW11ddXDw+PHH3/08PAA0z89PDxOnTqVkJBAIpFaWlp0dXVtbW3fvXv37Nmzz58/T09Pe3h4MDMzv3jxIicnh4uLy8jIaHx8fGVlpaSkZM+ePX5+fng8HoIgW1tbYWHhsbGx+vp6Li4uJycnPB7v7e3NzMzs5eWFw+EwGIyjo+Pr168bGhrOnj2LQqGWl5eJRCKFQkHEFOEvgugpwt9LT0/PlStXdu3ahUajgYsTgiACgeDk5MTAwMDGxhYSErK0tBQfH3/06FF9ff3k5ORr166Ji4sXFxd//Pjx9OnT2traGRkZxsbGoqKiPT09ra2tx44dY2Zmvn79elhY2LVr1xgZGS0sLDo6OiAIcnJy2rx5s5KSkri4OAMDw8GDB1NSUiorK1VUVFhYWHR0dLS1tVVVVaurq+fn53V0dLZs2WJmZvb69Wv6wTEEhD8HoqcIfy+9vb2BgYEWFhZBQUGwno6OjsbFxd24ccPW1jY8PHx+fn5ycjI1NfXRo0ehoaGhoaFlZWUEAmFhYSEkJMTZ2TkiIiI4OLigoACCICKRGB0draurGx0dXVZW5u3tfevWraCgoIaGBiqVWlNT4+Tk5OLiEh4efvv2bUNDw5KSEiKRWFlZaW1tffHiRWdn5/LycuC3fffu3aVLlywsLLq6uigUyn+zmhD+ESB6ivA3QqPR8Hg8FovFYDATExNkMhkMoy8uLmIwmMnJyfHx8ZGREeD6pNFoExMTXV1dU1NTcArLy8tDQ0O9vb1gOipgaWmps7Nzbm6ORqMNDw9jMBh4TwAKhTI3Nzc7O0uj0aamprq7u+FhKAwGU1tbOzY2BpdtdXW1o6Ojvb39P1glCP9kED1F+Bv52iNJv4qU/uA3r/z6IP3C0z+SHXzX76eDeE4RvguIniL8jdDvM/L1h29e9i+TWpcO/ZL838mOPvF1V0KIniJ8JxA9RUBAQPg+IHqKgICA8H1A9BQBAQHh+4DoKQICAsL3AdFTBAQEhO8DoqcICAgI3wdETxEQEBC+D4ieIiAgIHwfED1FQEBA+D4geoqAgIDwfUD0FAEBAeH7gOgpAgICwvcB0VMEBASE7wOipwgICAjfB0RPERAQEL4PiJ4iICAgfB8QPUVAQED4PiB6ioCAgPB9QPQUAQEB4fuA6CkCAgLC9+EfqKf0cdZWVlbKysrCw8NdXFy8vb2LiopGRkbGxsbGxsYyMjJiY2M7OjrW3Y7H49++fZuWljY7Ozs3N/f27dugoKDOzk76aygUSktLS3p6ekpKyrpTf4W1tbWmpqaMjIzKyko4VP0fZHl5uaamJisrq6OjY21tDT6Ox+M/fPjw/Pnzvr6+34kMCvN13Lp/qxj0LC4utrW1VVZWjo6O/rkUqqurx8fHf6skfySK3+8A3zgxMdHU1EQkEv9cOr/P9PT08vLyH6n53wIu5/Ly8sLCAnycRCJRKBT6C/7i//UXb/8HsLi4CN67P10P/0A9pVKpoDqwWGxwcLC2traSkpKMjIyKioqdnd2dO3fCw8PLy8svXry4d+/e2NjYdbfPzc2ZmJjIy8v39va2t7fr6uoyMDAkJCTQX0Mmk1NTU8XExA4ePJiYmPi9Sr68vOzr68vNzW1tbT0yMvIH7wI/dnx8/Pr160ePHo2JicHj8eAUlUrt7u42MjJiYmKKiYkhEAj/MimQGoFAWFtbo2+W/oQilJeXGxoaysvLp6Wl/bv3QhA0MjIiKysbHh5OJpP/eEDpPw6NRpufny8qKrK0tNTW1p6YmPjTSX2TgYGBmJiYO3fulJWV/RWxptFoFAqlsLDQzc3t7du3EASRyeTa2lo/Pz/wkMB/ze8H0/6XufxXxPR/g4JTqdTx8fHMzMx79+6VlZX9lVL90/QUfiwmJibc3d0lJSVdXFyam5shCFpbW8vNzVVRUZGRkamqqrp3756goODXakilUjMzM2NjYxcWFkZGRh48eMDIyPj1ZWNjY9ra2tzc3MnJyd+r8EQiMTk5ee/evWg0GovF/lv3EgiEBw8e7N69OyYmBn5719bWuru7XV1dd+7cGRQU9AffajweX1JSMjk5CUEQhUJpbm7+8OHDn3jCSktLxcXFmZmZY2Ji/t17IQhqampSVVUNDAz8/WYAj8ePjY39OR0ZHBx0dnZmYmI6evTo2NjYn0jhdygsLDx8+PDmzZuDg4NxOBz9KRqNtrCwMDs7u7q6+keSIpFIampqP/zww4MHDyAIIhAI0dHRx48fb2xsBBcsLS1NT0//RWudQqHg8fi5uTlg9v6t0Gg0Eom0tLT0Vyz37wWVSq2qqjp27BgDA0NERMRfSeofqKcQBBGJxNDQ0P379z979mxlZQU+S6FQioqKhIWF6+rqYmJiJCQkYmNjcTjc/Pw8Ho+n0WhUKpVEIs3Pzy8uLkIQtLq6mpqaum/fPnr7FI/Hz8zMTE1N3blzR1JSMiUlhUKhkEgkIpG4srKCw+FAd5tAIExNTc3MzMAqtrq6SiQS19bWVldX5+bmcDjc1w/T/Py8kJCQsbHx6Ojo4uIiDoeD3xAqlYrD4UD/kb6rSyaTFxYWFhYWXr16xcTEFB0dTa+bVCr106dPHBwcr1+/JpFIKysr6zqJOByOvpALCwtZWVlXrlyprKwkEAgVFRVmZma3bt0CFQJ+xeLiIr3GgV9Bo9HW1tZA5wAuWGBg4IULFzIzM8FXcBzOmkwmA0MY/u/WeRuWlpbo/z74LrjeZmdn4+LibGxshoeH1z0GcFIUCoVAIMC3wKdoNBqBQGhubra2tjY0NMRisbCOUKlUek2Bk1pbW4OP0x+kTxz+QCKRXr9+vWfPHj8/P6CncNZzc3MRERHPnj2bnp6GvsXXVVFQUMDBweHo6AiOLC4uFhUVzc7OQhCEw+GePn0aFxf3zaT+CCCvhYWFjIyMhIQE+jr/+xwIDQ0N8GtFo+NPZ/HNe/9ggiQSKTIyctu2bYGBgf8yx985+8/U09bWVllZ2SNHjvT29q67AIfDFRQUzM/PP378WEZG5vbt28HBwVZWVgEBAfPz8yQSqbi42NHRETZI09PTWVhY4uPjwdeJiYnw8PDr16/b2tqeOnVKXV29tLS0paUlJibmyZMn0dHRnp6ebW1tJBLp5cuXlpaWDg4O8fHx8/PzRCKxqKgoNDQ0MzOzqKjIwcHh3r1761QAgiAikSgsLGxsbJybm+vm5vbgwYPW1lbwu2praz09PY2NjR8+fNjd3Q3/r2VlZY6Ojj4+PnZ2dszMzLGxsevs0JqaGl5e3oqKitLS0sDAwJKSkuXlZZAmBoOJjo62srKKjY2dm5vD4/GJiYmnTp06ceJERETE27dvr1y5wsbGpqKiUlRURCaTFxcX37596+PjExsb29fXBwr88ePH1tbW6urqvLy83t5e+gcuPDzc0tKyrKyss7MzLy+vuroafldnZmbKy8tzcnIKCwuBW5D+3SCTyRgMpry8fHJykkajLS4uDg8Pj42NDQwMFBYWlpaWzs3NQRCUlpZ2+PBhSUnJly9fLi4uDg4Otre39/T0fP78ubGxkUKhgHp79epVRUUFUB84i8bGxtzc3JSUFB0dHRQKNTIyUldXV19fTyQSSSRST09PS0sLgUCAxXdiYqKoqOjDhw9EIhE+iMFgCgoKysvL6X3WS0tLlZWVDQ0N+fn5rKysAQEBwAMD7lpbW8vOzj59+vSDBw9gJwOBQOjr62toaID9d+ve2+rqal5eXicnJwiCqFQqaIpAB//ly5cyMjKenp5kMhn6tWFbXV2Fm7e1tbW1tTUymQyOwwdJJBJwwoLsKisr1dXVLSwsJicnwS30V1IoFJAvaFTAQdBGAnuCRCLR+4hASUAKwEyBEwH/r6+vr4SExPz8PFwA8HNAgqurq3D6NBqNTCaTyWQ4Xzijr/UU5EUkEundRGQymUgkrq6uwgUm/wpcUQUFBWxsbAEBAXCNgeOgcaWvT+i3+afpKSAzM5ORkfHSpUug/aevcbiKg4ODWVhYJCUlAwMDdXR0+Pj4ampqCARCeHj43r179fT0wC2vX7+G7dPx8XEfHx9NTc03b968evVKTExMWFj45cuXz5494+HhYWdnV1ZWvnjxYmlp6evXry0tLd+9e/fs2TMhISEnJ6e6ujrQtRQVFXV3d7927RoXF1d8fDz9ewhB0MrKioiICCcnp5OT0/Xr10VFRU1NTXE43PDw8Pnz5y9duuTh4aGgoGBpaQm6ip8/fzYyMjI0NIyOjr58+TITE1NcXNw6PW1oaNi5c6eQkJCmpqa4uPjJkyeTkpIgCOrr63NwcPD19Q0MDDx79qy9vf3IyAgosKCgoI+PT25urrKy8ubNm3V0dLKyslZWVu7cuWNubh4aGqqpqamurv7x48fnz5+LiooKCAhISUkpKytHR0fTZ/3kyRMhIaHTp0/r6upKSUmdOHHi+fPnq6ur09PTgYGB9vb20dHRGhoaampqbW1tEN0rUVFRoaqqeujQoaKior6+PjQaLSIicuHCBR0dHSUlJT4+vvj4eBKJ5Ofnt2PHDlFRUXt7ezc3NwUFBVD4gwcP6unpTU9PBwcHX716NSAgQF9f/9KlS01NTaBgz58/NzY2vn79uoaGxu7du42NjScmJu7evSsgIJCcnEylUp89e3bmzBldXV0MBgNBUGpqqqGhoZGRkZSUlJKSUnl5OQRBubm5tra2hoaGsrKylpaWwJs5NDR069YtBQUFIyMjYWHhHTt2hIaG0utpb2+vgoLCxo0bxcXFHz58iMViu7u7r1+/rq2traKioq6unpubu+6pgCCovLycm5v77t27EAS9e/dOV1dXTU1tcHCwra1NRkZm48aNp06dio6OXl5efvPmjZWVFRqNVlNTCw0NnZiYiI+P19PTMzEx0dLSMjAwyMrKysvL09PTs7KykpOTi46OJpPJnZ2denp6mzdvZmZmtrGxsbKykpCQePnyJQRBycnJ4uLi9vb2WCz2zZs32traVlZWV69elZWVjY6OHh0dffTokY2NzaVLl9TV1fPz8+Eyg3dtfn4+ISFBVVVVT0/Pxsbmy5cvi4uL3t7ezMzMGzZsOHfuXGZmJnhiQf0MDw+7uroaGRlduHDB2tq6s7MTh8PFx8ebmZnZ2Ng4OTnJycmdOXMmJycH+qrhmZyc9Pf319bWBn2O3Nzc1dXVqakpJycnKSmpy5cvW1lZDQwMjIyM+Pn5Xbp0ydjYWE1NTUNDo6am5t27d5ycnOHh4SMjIzY2NhISEmpqalNTU0ArTp8+HRIS8i+t3X+anoIfnJyczMDAcOXKFWCS0J+FayQwMJCHh+fGjRsDAwNpaWm7d++Ojo4mEAhlZWW8vLxKSkrgMno9TU1NFRYWjoqKAo2ng4ODkJBQcnJycXHx0aNHT506lZaWVlpampOTo6qqKiwsHBgY6ODgwMDAsGXLlqKioujo6J07dyoqKtbX13/+/JmVlfX69ev0I7YQBOHx+BMnToiLixcVFdXU1KipqR0+fHhycrK1tfXixYvJycmDg4OysrLHjh0jEAjLy8taWloaGhqfPn2anJwMDw8HzkoSiUSfZn19/e7duy9dupSVlZWVlSUqKiorK9vY2BgXF8fDw3P58mVXV9fdu3f/9NNPL1++bGtr09bWlpOTKygomJqaun37Njc3d1JS0vDw8Pv374WEhMTFxR0dHUVERH7++WdnZ+fS0lIlJaW9e/dev349MzOzsbGRvpJjYmLY2NgUFBTS09NjYmKEhISUlZX7+voyMjKOHDkiKSlpZmbGzc3NwMDg6+sLT2mg0Wh9fX02Njb/8z//k5iYODMzc//+/V27dp04cSI5OTk9PZ2dnV1bW3thYSEvL09MTOzSpUsFBQXFxcX6+vqbN28+e/bs48ePX758+fTpUykpKX9//46OjqCgIG5ubgcHB+AdlpWVdXZ2rqioCAwM5ObmtrOzm52dffr06aZNm+7cuQNBUGFhIQ8Pz5EjR3p6enp6eoyMjK5du1ZQUGBra/vzzz8nJSX19vZaWVlpaWlFRESoq6tv2bIlNjZ2dnbW3t5eQ0MjJSXl9evXysrKO3bsCA4OhjsENBptdnY2PDx8+/btmpqaRUVF3d3dN27ckJKSevXqVVJS0tGjR0VERCoqKtY92EBPnZ2dIQiqqamRkZH54Ycf6urqJiYmQFfpzp07VVVV9fX1EhISt27dysnJkZSU5ODgyMvLe/funaCgIDMzs5KSkpubm5+fn7q6ury8fGpqqomJiaSkZGlpKRaLffTokYCAwJkzZ1JSUt68ecPCwmJpaQlBUGlpqbCwMDc3d1dXV3Nz87Fjx5iYmDQ1Nc3NzV+9epWcnGxvb5+UlBQSEsLJySknJ9ff309f8mfPnh09evT27dsxMTFcXFweHh7z8/Pp6emCgoLs7OwhISGtra2wvbm4uOjh4XHgwIG4uLjY2Fg+Pj53d/fV1dVnz56xsLBwcHC4ubn5+/uzsrKiUCjQBtMTGxsrLy8fHBz88uXLU6dOSUtL9/T0+Pr68vLyent7P3jwYO/evampqTMzM+Hh4Xv27Nm3b5+GhoadnV1fX19hYSEHB0dISMj8/Pz9+/c3bdokISExMzMDQdC1a9eEhISA2+r3+WfqaWFhIRsbm6Ki4rpRHfrmxc/PT0pKCrTAbW1trKysnp6eJBJpfHxcRkZGWVkZXPb69WsWFpanT59CEGRvby8gIACPLfj7+6NQqOLi4q6uLlVVVWtra2AzxsXFHT9+3NDQMCkpKSYmxs3N7eHDhxgMJisrS0xMzMvLC4IgHA536NAhKyurdR605eXl48ePm5qaAk+rtbX1oUOHsFjswsJCfn7+kydP/P39T5w4ISIisry8/OXLF2ZmZh8fH3BvcXExMzPzkydP1ulpZWXlwYMHa2trwVdvb29paenY2Fhra2s9PT1nZ+f79++bmJjcuHGjuroai8WamJioqal1d3dDEJSUlKSlpfXlyxcCgeDq6srPz6+lpXXv3j0LCwszM7OMjAwCgeDh4aGvrw+bfvR6GhkZKSwsHBYWBr4GBARwcnKWlJS4ubmxs7M7OjrevHnT3NxcXV09Li5uXdMCOstgLKumpkZWVtbc3BycQqFQcnJyMzMzbW1tKioq5ubmwJ/79OnTkydPRkZGQhBEoVAsLS3Pnj375csX6Nfxw2PHjtXU1Nja2uro6IC3cWRk5MaNGzY2NjMzM01NTTw8PC4uLhAEdXZ2XhrpvicAACAASURBVLhwQUtLa2hoKDEx0dTUtLKyEoIgDAaTkJDQ2tr65MmTs2fPqqur+/r6GhgYCAgIREVF1dXVSUpKPnz4EIIgKpXq4+Oza9cuHx+fdb343t7eAwcOuLu7QxD07t27Y8eO2dnZwQ8VIyPjzZs319UG0FPQ3ycQCO7u7vv27auvr4cgKDAw8Pz581VVVRAEhYSE7Nq1y87OLjs7W0tLi5ubOzExcW5uztTUVE1NrbCwEIfDVVZWBgUFZWRk1NfXOzo6MjIygj+otLRUUFDw1q1bIEd1dXVFRcXZ2dmVlZWQkBAlJaWenh4IggwNDbm4uDIyMmZnZ8fHxy9cuKCurp6QkAAGJE6ePFleXk7/oj1//tza2np8fDwvL2/37t0WFhY4HI5AIBgbG4uKitK/mzQaDYfDpaSkuLu7LywsVFRUcHBwaGhoEInEpqYmUVFRFAoFPHhaWlosLCy5ubnr3h1dXV1ubu6YmJiEhARFRUVeXt7a2tqEhITHjx8vLCwEBgbu2rUrPDycSqW2t7cfP35cXl6+o6MDiGZhYSE7O3tAQAAEQQMDAxoaGsALRCQSzc3Nvb29gTvl9/mn6Smgo6MDhULt378fOB/X0dbWhsPhgA0PHKNfvnxhZWX19fUlkUhDQ0NSUlIXLlwAFwM9BR1kfX19ERERUPsQBHl7e6urq1dUVLS2tiopKcHmcGRkpKioKP34AIVCoVAoSUlJEhIS/v7+EARNT0/z8vKC15i+bEBPDQwM5ubmlpaWLCwsDh8+PDs7SyaT4+Lirly5cu/ePQUFBXFxcTBwRD96npeXB/yn60aNgZ5+/PgRPOUhISHKysrBwcGamppeXl7d3d2dnZ39/f1AhUdHRw0NDS9evAiqLiYm5uLFizU1NdPT02g0Goy/dXZ2NjU19ff3gxmRaDTa3t5+YGDg66oGogOPmWZnZ+/atSs9Pf327dtnzpzp6OhobW1taWnp7OwcHR2lH+Mik8mgZwCq8f3793JyctevXwc/TVpa+vz587Ozs42NjfQ1Hx4efubMmaioKAiCMBjM+fPnlZSUwOyOmZkZS0tLTk7OsLAwMTGxu3fvgpofHR318PCwtbWdmZmpqanh4uICfere3t4rV66YmZmNjIz4+vrevHkT+IthHB0dz507d/v27aCgoEePHqWlpQ0NDUVGRsrIyID5YSsrK3FxcaysrCkpKcDlCqvM58+f2djYXF1dqVSqp6cnExNTUFAQOPX+/Xtubm5gxdNnt05P/f39WVhYgJ66u7ujUKiamhoMBmNqaiomJnbz5s2AgIDg4ODU1NTe3l5w3MPDA/ReIQjq6ury9fW9e/euoaHhli1bHj9+DEFQXFzcli1bHj16BIQDOK+wWCwOh0tISLC0tATufkNDw3PnzoHpH+Pj42xsbDo6OqGhof7+/o8fP87KysJgMLBzEzzqOTk5QUFB1tbW3NzcLi4uS0tLMzMzOjo6wsLC8J8O18/c3NybN28eP34MDF51dXXQ1KmoqFy7dg1YM5qamgcPHiwsLKSvop6eHklJSRERkbCwMH9//9DQ0KSkJCwWu7S0lJ+f//jxYz09vT179sTExKytrfX09AgLC6PRaDj3oqKi/fv3g/EoEon05MmTffv2JSYmvn//3sTEJCUlBfqWX3sd/zQ9Bb92ZmbG09Nz37599+7do59MDgZP3NzcJicnY2NjJSUlnz17BkFQW1sbGxtbcHAwmIkmIyOjpqYGbsnNzWVlZQVvyPXr13fs2AFsVQiCvLy8UChURUVFf3//xYsXLS0tQbeuoKBAXFzc2NgYg8GsrKyMjY0lJSWBCW5SUlKPHj2CIGhpaenQoUMODg7r5u1TKBRhYWETExPQhtvY2AgKCi4sLHz48EFERCQ6OppEIpmbm588eRKHw338+HHv3r329vbgBSgtLQX26TrvW1VVFTs7O9xbsbKyOn78eE5OjqGhoZycHDznpqKiora2dmRkxNDQUENDY3BwEIIgR0dHdnb2uro6CoXi5uZ2+vRp4LeCIKi/v7+8vHxmZkZVVdXe3h68YOvw9PTk5+eHm5YnT57w8vIWFxe7uroKCQk1NDSA49XV1bW1tfRVAWatsbCwgD+orKxMQUHBwcEBDK/LysoqKysvLi4CPbWwsACvZVRUlKSkJPDhjo2NiYuLCwoKAvt0YWHBxsaGl5c3Li6On59fRUUFCFZbW5uent7169dxOFx1dTVsNgKnm5WV1eTkZEhIyMWLF9+9ewfKhsPhurq6HB0dZWVlYROJQqF0dnbeunWLl5cXlBn6dRAJrBmBhzIoFEpeXh4LC4uHhwcEQe7u7j/88AP4DEFQcXExBweHurr6ukUQFRUVPDw8wBdBIBACAwNZWVnBfxccHGxqatrf3z89PW1sbKykpAT+O1DUoaGh4eFhTU3NR48egUG8hYWFsLCwCxcuvHnz5t27d9zc3MA+BQoC/yJ5eXngXlhcXAwJCTE3NweuZAMDAyUlJaBrIyMjPDw8oEMAmJmZmZ6ehqd8QBBUW1trZmZmaWmZm5urrq7u5eW1vLw8Ozt7+fLlkydPrpsvQSAQkpKS5OTkfH19h4eHZWVlL168uLCw0NjYeOHCBXNz8/n5eQiCLl26xMXFVVxcTF9FdXV1R48e1dHRgadbzM3NkUikgoKC8+fPe3h4pKWlsbGxJSQkkMnkvr6+U6dOGRoawn9fRkbGvn374Iatvb1dSkpKRUVFW1vb19cX2Ob/5/QUZmxs7Nq1awICArdu3fr8+XNPT09fX9+LFy/Mzc2jo6MHBgZcXFyOHDkSEBCwsLCQm5v7yy+/2NjYTExM1NfX8/Pzi4uLj4yMLC0thYSEbN261d3dfX5+PiMj48CBA/Ly8vX19d3d3YaGhuD9fPv2raioqIqKSkNDAxhsMTMz2759u56eXkBAgKenp6enZ09PT3R0NB8f361bt2ZnZ9va2lhYWLS0tLq7u+FHikwmd3R0HDhwQEFBobe3d2hoSENDg5OTs7y8/MGDB4cOHfL29s7IyDh+/Dg7OztYdyQtLX3kyJEXL14MDAxER0dv2rTJxsZmnYFQVVW1b9+++Ph4DAbz5csXBQUFExMTMpn89OlTVlZWKyur5ubmrKysmzdvZmZmYjAYQ0PDs2fPZmZm4nA4b2/vXbt2BQcHDwwM1NbWCgoKXrhwobq6uqKiwtvbOzo6urOzU0VF5cKFC1VVVV9PGzIyMtqwYYO3t/fk5GRLS4uenp61tfXo6GhKSsrBgwcvX7785cuX2tpaHR2d+Ph4eBkCBEErKyvx8fE7duwIDAxcXl7OyMgQERExNTVdWFjA4XBiYmKSkpJgRF5OTk5TU7OhoWF5ednHx4efn9/Pz49MJi8vL9+/f3/Lli1hYWFLS0utra3Gxsba2tpjY2P37t3j4eGJiIgYHx/PysoSFxe/fPlyb29vbW3twYMHzc3NR0dHCwsLpaWlVVVVW1tbMzMzDx8+rK+vPzo62t3dHRYW5uXlFRUVdfToUZDg0NDQy5cvAwICUlJS+Pn5DQ0NZ2Zm8Hh8QkLC3r17k5OTge0PS0Z0dPS2bdvs7e0nJiYyMjK4ublBz5pAILx+/frAgQO2tragbYYpLS3l4OC4efMmBEHgp+3du7empgaCIAcHh9OnT5eWlg4ODvr7+x85ciQ1NXV6enpkZCQ8PPzx48e9vb1KSkqurq7AuZSVlYVCoYKCggYGBp49e7Z379579+6BqR379u2LjY2dmJggk8koFApUeENDg66urqamZl9f39ramq6u7rFjx4B7Z2pqSkpKSlNTs7KycnZ29sOHDx4eHh8+fKDvIYFlJm1tbU1NTSdPnjQ3Nx8ZGRkfH9fW1hYUFMRisQQCAQzxQxDU09OjoqLCxcXV1tbW1dUlICAgJycHFrDJy8uj0Wgwb09dXZ2dnZ1+7AuCoPb29rNnz3JwcCQnJ8/Ozg4MDHh5efX395uYmAgICNTV1b169WrXrl1eXl4rKysNDQ1Hjx7V09Oj/TrD0t3dfdOmTSEhISC1hYWFkJAQDg6OXbt2rXMs/A7/WD2FIGhqaio4OPj8+fO8vLwSEhIKCgoXLlxIT0+fnZ1NSkoSEhLavn27gYFBRkaGgYHB1q1bmZmZU1NTPTw8duzYsXPnTgsLi4KCAmFh4a1bt3JwcKSkpJBIJDCUz8XFJSoqKigoePLkyUuXLklLS+/cuXPv3r1Xr14Fg7zV1dUqKio7duxgY2NDo9Hd3d29vb2XL1/evn27lJTU06dP3dzc9u3bx8rK+vjxY9gum5mZuXr16vbt25mZmSMjIxMTE9nZ2Xfs2KGrq5ueno5CodjY2OTk5KSlpbdt22ZiYjIzM/Px40cxMTF+fn4NDQ0BAQFGRkZhYeF1A8QdHR2CgoICAgJGRkby8vJ6enrV1dUQBGGxWDQavW/fPg4ODjExsbi4uOXl5fn5eUdHRyYmJk5Ozg8fPnz+/BmMP2hpaWEwGC8vL3Z2dnZ29v3795uYmLS0tMTGxvLw8Ozevfvhw4ewyw/W0/DwcD4+PklJSRsbGzQaraysXFxcTKVSp6enra2tf/nll/3793NxcZmYmHR1ddE3/j09PZaWltu2bVNRUcnMzLx16xYjI6O0tHRZWdmrV68OHToEXHifP39WUVE5dOiQurr6u3fv9PX1t2zZYmpqOjg4SKPR2tvbz507Jy0tnZCQcOfOHTk5uby8PBqNVl9fLyIiwsvLe/XqVS0tLSYmJnZ29vDw8P7+flVVVTY2Nm1tbUVFRXZ2diYmJl9fXzDB4Jdffjl//rympqasrOynT5+Wl5ft7Oy2bt0KBsSUlJTq6+sJBMKVK1e2bdtmZ2eXnJysqqr6448/SktLAxMVbuTKyspYWFj4+Pg8PDwqKytv3Lixd+9eBweH5ORka2vr8+fPv337lt4OWl1djYiI2Llzp66u7tLSEpgh8Msvvzx//pxGoz148ICFhUVRUdHPz6+qqkpKSoqTk1NTUxOFQhkZGbW2tpaXl7Ozs585c6a+vp5KpT5//nzPnj1g6siZM2c2btx44sSJioqKz58/nzhxQkpKytbWdnx8HI1Gc3BweHt7u7q6cnBw8PPzZ2dnV1VVSUhIHDp0KD8/n0qlglUkrKys/Pz8aDRaRkYGlJC+8E5OTj/99JOGhoaysvK2bdsOHz6cmJjY2dlpbm6+b9++8PDwhoYGeBZdU1OToqLitm3bjI2NdXV1t2/fzsPDU1paWl1dLSAgoKysPDo6isfjFRUVt2/fHhQURD/gvLa2FhwcvH37dm5u7qtXr5qYmKDR6MHBQQsLiy1btmhra0tKSoIf293d/fjx440bNyooKAA/1cLCAlgJee/ePfDu0Gi0np6eAwcOSElJtbe3/0HN+SfrKQRBS0tL7e3tZWVlFRUVNTU1TU1NwAjCYDC1tbU1NTWdnZ0TExOtra21tbUVFRXj4+P9/f3V1dXV1dUtLS1TU1O1tbXgFOjsEAiEL1++AKH58uVLe3t7a2trXV1ddXV1VVVVS0sLSJ9MJg8ODlZWVpaXl4OeAoFAaGtrA2UYHR3t7e398uVLdXX18PAw7OcmkUgtLS01NTXV1dVgn4Gampra2trm5ualpaWenp7y8vIvX750dXXV1NSAUVEKhdLR0VFZWVlfX19VVVVXV/flyxe4wwVBEI1GA+78hISEwMDAjIyMgYEBeGr9yMhIUlKSv79/Xl4eUEMKhdLf3x8SEgJ2MCCRSIWFhf7+/jU1NWtra3Nzc5mZmXfv3g0LC+vt7cXj8e/fv//06VNRUVFFRQXoTsL50mi0ubm5hoaG58+fgwTb2trguVxDQ0NPnz4FSfX09ND3EMEy2SdPnnh7ez969Cg7O/vly5dubm7R0dFNTU1v3rx5+PChj49PYWHhyMhIQUFBSEhIVlZWRUUFGP2LiYkBY01UKrWvry8xMTEqKio2NjY/Px/kvra2VllZ+fjxYz8/v6D/x957x0WRLe/D3A33rrq7BkQBQVCCIIgJyQhIkixBQBQkR8lRySAgQUSCAoIKkiXn5JKT5JxzGoIMeWCAmfeP+my//AbXdd296Xutv7Dt6a4+fbpOnQrP8/ixq6urn59fb2/v5uZmaWmpl5cXhN6eP3/u5eUF3tbg4KCrq6u4uPi9e/fy8vLA/xocHHR0dBQSEjI1NS0qKoL32N3d/eDBAwkJCXNzc3d3dzU1taCgIIKsIxqNfvz48e3bt1+/fr28vDw9PR0QECAuLq6kpKSpqfnu3TuCdon29nYTExNubm4xMbHIyMjs7GwxMTF+fv6HDx/Ozs7W19erqqrKyMgkJCSsrq5mZGRISUmxsbHp6+vX1tbOz89DqbWAgEBgYODMzAx46Pz8/Jqamk+fPlVSUjI1NR0bG5ucnHRwcBAXF/f29l5YWCgqKlJSUlJTU3N3d9fX19fS0kpPT/fw8Lh27Ro/P7+Tk9PAwAAOh0OhUJaWltzc3Nzc3IaGhhDS3S3Z2dlCQkJiYmKQ/5SVlc3Ly1tbW4Pw1/379ycmJhD/dGVlBdIM0tLSsbGxOjo68vLymZmZb9++FRQUlJWVffbsmbOzs4SEBC8vr7a2dl5eHkG9lJ+fn5CQkIiIiJ6eXn19/cbGxosXL3h5eW/evGlkZKSgoHDnzp3CwkIHB4crV65cu3YtODh4e3u7oaHhzp07HBwcUlJSWVlZcLXZ2VlRUdHdjsLvyv9xe/pVENne3ibIfYHgcDiCegA8Hr97643H4wk6PhcXF5HSceRMqPT+6K2hBnDvXXA4HHIpguPQhLawsDA7Ozs7O4tGo6FpbW1tbWZmZn5+fn5+fmFhAWq8wSFaWVn58OHDwsLC/Pz87lDs+vr66Ojo3NwcQeRrfX0dhULNzc19+PAB2Vzv7OwsLS2h0WioCV9aWkK2rktLS83NzQRpt4WFhZaWluHh4d0HP3z4UFtb29TUNDU1NTQ0tLvJDRE0Gt3b24usQGtrazU1NWVlZS0tLQRdczgcbm5urrGx8f3791VVVW1tbWNjY+/fv29sbOzs7FxbW9va2urr62tpaYHPHovFdnd3V1RUgFabm5udnZ2NjY11dXUdHR3wvubm5urr66G0s6+vb3R0FGrmx8bGQG2oYO/p6WloaBgaGhoZGenv75+ZmWlpaampqYGng1AmHo+fmppqbGxE7kggS0tLra2tTU1NQ0NDgIkBb2d5efn9+/ednZ0Ez7u0tFRfX9/Y2LixsTEyMtLe3j49PT0yMgLdFq2trRUVFbW1tRAp2tsRs7y83NraWlNTAwUqeDwehUI1Nja2tbWNjIxA9dvU1FRnZ2d9fT0kk3d2dmZmZpqbm+vr60tKSpDoc2Njo4SERFFR0e+WnSLy1Z5+la/yVb7K/y+Tk5NBQUEGBgbXr193cHD4Q0gaX+3pV/kqX+V/VABHBvkn+KG1tbWCgoL79+8XFxf/o2ic/3fs6W6f/HfLGr7KV/kq/8uC+xXSk6CbCw7GxcWFhIQg4Yv/uf0+PDDgNiHwS/9upf4fgRbV/zSt9gqATew9jvsVPupfr9JX+Sp/ufyK5IH7XYiTPyT/R+wpHo/HYrElJSU2NjbJycn/bl3+H4Fu9Ldv3/7yyy8EOJj/UbK2ttbS0vL27duhoaHddhOLxY6PjxcWFpaUlPxR1oB/owC84dzc3N482F8lAF2IRqMhXwfptZWVlX8Bfuh/nQC46sLCAqzWGxsbMFaf+MnOzs7Kysry8vLa2trS0hL4SV9w3/X19eXlZQKQoE+4XBgM5tOKfUK+xJ7uVeUPPec/yUfr7e01NTX96aefkAbkL5O/fMnCYDCWlpbk5ORaWlofTYDuVYAgdvFP9QqR28XHx9PQ0Fy4cKG0tHR3O0BHR4eSkhI1NbWqqupnsgZ8YvT+ZVuHpaUlX19fISGhd+/eEdwdUeBPalJbW6utrX3t2jXocF1fX1dXV3d1dd2dwfjzD4u8i//8zc1vyc7OTl9fn7OzMxsbG0BzpaWliYuLGxgYfAJRe35+PiAgQE9Pz9zcXFdX18/P7wuWxuHh4YCAAFVV1ejo6M/8SXh4+N27dwn6fT9TvtCe/u6Rf72srq4mJiaSkZFpaGj8mesgE7e3t9fa2vq3EH8//2rb29vv37+no6Pj5+f/nJeEKPDu3bvAwMB/wRYbbtHf33/79m1iYuLdNX04HG5hYSE6OvrixYtiYmJ78WR/SxYXF4uKivYGp0DKy8uLi4v/EuV/S9bX1wsKCnx8fKCWfnFxEWAK4NEqKyuhme3P3ALwt0hISJA2UG1t7cDAQPBuxsfHS0tL/+Qt8Hg8FouFIvY/eZ1/o+zs7DQ1NamoqBAREUG/cmho6I8//sjCwvIJ8gUMBlNYWMjJybl///4bN26kp6d/vuOPwWDGx8exWCx0jlBTU/8uUDQiT58+lZCQaG5u/gKz9uX7/YaGhsDAwMzMzN172LW1taSkpPDwcKh+3y1lZWUvXrxAPrBPr7cYDKa1tbW1tXX3QTQaDYCyAwMDu0vH8Xg8CoXq6OhoaGjg4OD4hD0Fn7+/v39ycnL33WGru/t2ExMTBgYGR48ezcnJgfvuVXtiYqK2tvajtb6AU7V713D9+nUBAQEC+/KJEVhZWTEwMBAWFt59cHNzc3R0dPcUJPBkkb8HBwd/ly1qY2MDaS+B30ILc3R0NFJeCsenp6dv376tqKj4maQgW1tbr1690tHRgQZzgnc9PDxsa2uLNLnvld96qC8TuEJVVdX9+/ehMQyPxxsZGf0ZQHtE4uPjWVlZnZyccL9idyIzMzc3V09P78/s/eGaa2tr9+/f//yV7NNX+/QJH3WVPucVfPocHA6HQqE8PDyIiYmhd7OqqkpSUlJaWvrTsxSLxdrZ2ZGTkzs6Ov7ufN4tU1NTdnZ2ML2Tk5NlZGT8/f1/V2E4ODU11dDQgFTX/u6vdsuX2FMMBhMdHa2kpKSqqqqsrBwQEACF4u3t7R4eHoaGhs7OziYmJh4eHikpKcvLy1NTU/Hx8QDSY2lpmZaWtrCw8FvvaXt7u7S01NLS0sPD4/79+yEhIdBHHxYWpqen5+Pj8/DhQ11dXVNT0/fv3+N/JTvy8vJ69uyZtbU1KSmpgYEBwTUBYMba2trS0jIgIMDMzExdXf2XX36B25WXlzs6Onp4eFhaWnp6enZ2dm5vb8fHxx8/fpyIiEhdXb20tBTphwOdNzY2YmJi7O3tHR0dnZycoI94dXXVz8/v0aNHkZGRoaGhenp6uxH4BQUFRUREOjs7a2pqPDw8/P39Ozo6cDhcX19fWFhYbGwsgv2Dx+PRaHRcXBwtLe2pU6fi4+M7OjqwWGxGRoazs7ONjc2DBw9yc3N3t4QjAuwDXl5eOjo6lpaWADEHKNHPnz9//vy5k5NTamoqxHOdnJzMzc3Dw8OR/WlKSsrJkyffvXtHYE8HBgYAyDkkJAR6k6DTLC8vD3qr1tfX6+rqnJ2dExISUCgUdC6SkpJqamrW19cjSu7s7DQ3N+vo6NDS0goJCYFJRaPRMGIBAQGZmZkEBCc4HK61tfXx48fe3t7v3r1bWlqKiYmJiYnJzMwcGhqan5+PjIz08fFpa2urrKxMTEx8+/ZtaGhoVFRUT09PYWFhVlbWhw8furu7lZWVT506ZWNjEx0d7ezsTEFBISwsnJ6eDsthTk7O/fv33dzcoCN+YWGhtLS0tLS0r68vOzs7MDCwpKTko99zYmIiLy+vi4vLxsZGf39/ZWXl4ODgwsJCcXHx9evXT548GRERAZwFPT098fHxUVFRAKy3trbW2dlZWFjY0tLS0NBQXFw8MzOzsLCQn58fFRWVnZ0NL2V4eNjHx+fYsWO2trbx8fGJiYnl5eXQ6V9TU5Obmzs+Pg6QEZ2dnVDxnpeXhyBbJyUlJSQkvH///qM7ZTQanZubGxUVVVpairgF6+vrcBAi6QTfaW9vb25ubn19/dzcXG9vb1ZWVmZmZnt7Ozxgeno6QhhcW1sbGxtbXFwMHfdYLDYyMvL48ePgn05MTJiamt66det3Oc2ioqJ4eXmhrX5ubm5qampnZ2dsbCw7Ozs/P/+jC/zExMT9+/dJSEh8fX0Bs9XOzg7wCjIzM1tbWzc3N+GhJiYmUlNT4+Li4EvB4/EfPnzo6uoaGRmBPpGurq729vahoaHy8vLdM/m35Evs6eTkpLq6urKycl1dnZaWFj09PSz7bm5ulJSUr1696u/vFxAQICIi0tfXX1hYePPmDRMTk7GxsYuLy4kTJygoKPLy8vC/YeyXlpYcHR3PnTuXlJT08OHD06dPx8TEzM/PGxsbHzp0iJeX18jICIg9zM3Nt7a2qqurRUREnJ2dCwsLjY2NDxw4cO/ePYJrfvjwwdfX9+eff/7hhx/AzJ04cUJHR2dpaamzs1NZWRkAgP39/U+ePGlsbDwxMZGRkSEoKAhomDU1Nbvf+traWmJiIgcHh5mZWVxcnKKiIjs7e3l5+czMzLVr14iIiPj5+f38/GRkZE6dOhUSEgK2SVBQUFRUtKurKzMzk46O7m9/+xugjWVnZ3NxcQFhFHKLmZmZ4OBgamrqEydOPHr0qLS0NDMzU1hYWEFBwdnZWVJSUlhYuLy8nKCzCIPBpKWliYqKqqmpmZmZnTt37vr164CJJyoqum/fPlFR0cuXL7u5uYWFhTExMVlZWdna2jIyMkZFRcFnExoaysjISADCjcfjh4aGbt68ycTEJC8vLyUldfz48du3bzc1NQUGBpKRkV2/fn1gYCAnJ4eMjIyenr6qqiorK4uJienw4cP8/PzwmLhfG0nfvXvHy8v7448/njlzxsHBYX19PSAg4MqVK/r6+kpKSnx8fJGRkQTfWFlZGRcX1z/+8Q83N7eZmRllZeUTJ07o6em1t7f39PSIiYkxMTGlpKQYGRkdO3aMk5NTXFxcW1u7uLhYWlr6MjVuHgAAIABJREFU6tWrzc3NNTU17OzsP/30k7q6uoODg6io6Pfff8/Ozh4YGAgrnI2NjYyMDDs7u7S0dGVlZXd3t5qaGhcXl7m5uY6ODiUlJS8vb0lJyd7pmpCQwM3N/fDhw9XV1ejoaB4eHgBGCg4OPnTo0KFDh1xdXaFBOSAg4MmTJ2ZmZsDv0NPT4+3tzcHBoaCgcOvWLS0tLVicVFRUgDXA29sbIG75+Pi+//57JSUl4IaQlpZOS0tbXV19/fo1Dw/Ps2fP5ubmiouLDQwMREVF5eXlRUREMjIy6uvrg4ODXV1dTUxMlJWVU1JSCBaqmZkZFxcXBQUFbW1tZWXliIgI6A2LjY01MDAwNTVFkA93S0ZGBi8vr5aWVnt7e0pKCg8PDz8/f3p6Og6Hi42NlZKSSklJwWAwKSkpbm5udnZ2t2/f9vLymp6e3tjYCA8PP378OPino6OjGhoaIiIiv2tPIyMjubi4AgIC1tbW4uPjzczMfH19nzx5oqurKyQk5OjouHeDWFdXd+bMmW+++QYgX6urq3V1dZWVlZ8+fSonJ3fnzh1oneru7g4ODnZxcbGystLS0qqoqMBisVlZWaKiosbGxr29vXV1dYaGhnJychYWFrKysm5ubp9WFf9l9nRmZiYrKys9Pb2qqkpPT+/nn38GX+/evXu0tLSwaw4MDDxy5EhKSsrW1paVlRUpKamWltbdu3fZ2NhOnz799u1b/C4Es92ytLRUWFj4+vXrurq6sLAwYmJiQNCqrKyUk5Pz8vICNBo+Pj4lJSXAgLl06RI4d42NjSwsLFpaWnt1npiYADhhcI21tLSuX7/+/v37wMDAc+fOFRQUwGkARZObm7u6uurv778XnxSPx/f29nJxcQEKER6PLy8vv3DhgqCgIBqNzs/PJyUlBYDniooKQUFBXV1diHwJCgoKCgpCPiomJoaKigoASRMSEgABi+AuIyMjkpKSV69exePx6+vr4uLiN27cgLEtKSm5dOmSlpYWAZtLR0eHjIyMtLQ0uCevXr2ioqIyMTFZWlry8fE5fPhwQkJCT0/P7OxsSkqKmprazMxMY2Pj6dOn7927t76+vrm5aW1tzcDAsNtTBhkaGpKVlWVkZAwNDUWj0T4+PmfOnAkJCZmentbW1hYTE4O9gqurKwUFBTg7JiYmQkJCZWVl+D0pPj8/Py4uLmDoKi8vZ2Bg8PT0XFlZmZmZERcXp6OjAydxt2RlZfHx8T158mR9fT0jI+PIkSMQsmxra7O2tk5OTh4aGjI0NNy3b5+GhkZZWVl3d/f4+LiUlNS1a9dAN09PT3C9cTgcMAUFBATAa5KTk7O3ty8tLX369OmPP/6or68/Pj5uamr63XffARqLra3twYMHAWeaQMCeurm5bW5u5uXlgUu+uLg4Pj5+48YNZmZmsBd37twRFxfPzMz09/fft28fDQ1NY2Ojn5/foUOHTp8+ra2tHRYWlpqaysXFBXwbEhISly5d6unpWV1ddXV1PXr0aEpKCh6Pf/z4MRMTE7CcDg0N0dDQaGhoTE5OFhUVsbGx7d+/X1FR0dbWtqCgQFNTU0JCIi8vDyw7BwcH0n8JUl9fT01N7e/v393dLSAgcO3ataWlpaamJjY2Nnt7e4DZRoDAEenq6uLh4bly5UpDQ0Nzc7OMjAwzMzNgTQUHB4OpamxsZGRkvHfvXk5ODhcXFxER0ZMnT8A/PXbsGGJPtbW1paSkfteePn/+nI2N7enTp2tra2FhYWRkZMePH3dwcEhLS5OWlj59+vReLoORkREVFZUjR45ERESgUKjW1lYJCQlGRsbw8HBvb28SEpLXr1/v7Oy4u7tfvXo1OTk5NjaWhYXl6tWrPT09SUlJhw4dOnv2bFFRUVlZGTs7+3fffSchIWFmZpaUlPRpVfFfZk+3t7fb2tqcnZ3l5eW5uLh++ukn+Gx8fX2vXLkSExMzMDDg4eEhLi5eV1c3NTWlqakpKysLJjglJaWwsHB3AnT3lwZ/LC8vA1aQkJDQ3//+96CgIDweX15erq6unpaWBmeKiIjY2tqiUKh79+7du3cP1t6mpqZP2FMFBQUED9zGxubOnTtFRUWmpqZUVFRIbiQiIgIwdTY3N588eWJsbLzXnjY3N5OSkjo7O0N4dHp6+tatWxcuXPjw4UNRURE5OTms6hUVFUJCQnp6ervtKcRPBwcHpaSktLW1JyYmbG1tjY2N92YtRkdHEXsKYP46OjrgOba1tbGxsZGRkRFEY3Nycg4fPmxvbw+KDQwMCAoK8vDwjIyMvHjxgpSUFLYFeDx+Y2Ojra3Nz8/v5s2b+/bt09XV/fDhw+Lioo6ODiMj494U3MDAwM2bN2VlZbu7u2EEAKdqcnJST09PQkICUDDc3NyoqKgqKysXFxdNTEyEhYVhnSDIqj9+/JiLiys2NhbmNBkZGYLtD+BeT548IYDFHB4e1tTUFBAQAP47Wlpafn5+2GBKSUmtra3hcDh7e3tOTs74+Hjcr6Xad+/ehVUTj8d7enrCGob/FYkd7GlUVNRPP/0kLi4uKiqqoaHBw8MDwdC0tDQSEpLQ0FAMBtPQ0HDmzBldXd298wrsqZOTEx6PR6PRjIyMampqQDeroaEB9hSDwXBzcxMTE9PT09PQ0JCTk3Nyck5PT1dVVVFRUenp6a2vr29tbY2Pj/v6+jY1NdXU1Fy+fJmLi6u7uxuLxQYHBx8/fhymaHx8PCcnJ9xueXmZkZFRXV19YWFhbm7uzp07DAwMKBQK+u65ublpaWltbGzAReDl5SVo9RkaGrK0tKyuru7t7eXk5GRnZx8bG2tra2NhYREQEMjIyMjKykLeCyI4HO7x48dsbGxRUVHAXws5ho2NDWNjYxMTE6AWJiUlvXHjhq2tLRcXFykpqa2tLRaLffnyJeKfDg8PGxsbq6mp/a499fb2ZmRkfPz4MQ6Hm5ycFBER0dTUBJRLf39/UlLSjIyMvQgA9vb2FBQUgIne0dFx584dCwuLzc3N3t5eSkrKBw8eAA8FGRmZpaWlrq7u+fPnqaioysrKsFislpYWDQ1NQ0PD3NyctrY2MzNzRkYGQg74aW2/xJ729/fr6OjcuXMHQoHHjh0D/7S1tVVTU5OXl1dHR0dRUTEvLw+LxQ4NDYmJiYFjv7W1tbGx0dLSMjk5id9VCLJ7ONbW1p4/f66goFBcXBwVFUVKSgqhk9LSUjU1tZSUFPjSREVFHR0dR0ZGbt26ZWJiAva0ubmZhYUFYcXYLRMTE/Ly8uzs7PBPiELOzs56eXlRUFAgQN/p6eknTpywsrLa2Njw9fXV09Pba1xaWlqOHTtmaGgIphaFQqmpqYE9LSgoICMjAzzjsrIyISEhQ0NDiLsJCQkJCQkBmgYWi01KSmJjYwsPD/f19Y2Jidmr8MjIiISExG57qqenB/Z0bGxMWVn5+PHjBB5Hdnb2Dz/8cO/ePdgBjY2NSUhIXLx4EaiiyMjIEHtaV1enr6//6NGj9+/fAz01oI3o6OgwMDD8lj1VVFQEqIjR0VEpKSkhIaHR0VFdXV0AfsXj8c7OzoyMjL29vYuLi0ZGRog9JRBfX19OTs6YmJitrS0nJydycnIk6JaUlHT58mU7OzuCBWZ7ezs2NpaKiurZs2eamppKSkoiIiI2NjbBwcHAH4PH4x0dHfn4+JAVd2ZmRlNTU1xcHLH1DAwMgDuVnZ2N+KeBgYH09PRdXV1DQ0OTk5OTk5Pw+FlZWZCaw+FwHR0dzMzMH7WniYmJPDw84DCur68zMzOrq6sj9vT8+fNoNLqqqgq+4Z6enp6enqGhodHRUSwWW1ZWdurUKTCOeDwePFx9fX03NzdBQUFJSUmwpyEhIcePH4eqr4SEBB4eHgCfXltbY2Ji0tDQWFxcXFpa0tTUPHfuHIwbbHi1tLRQKNTExMTIyMjQ0BCB5QJPX0FBwdXV9cqVKzw8PL29vZADICcnp6GhUVNTg1AvgYyPj8vIyCgqKk5NTWlpaVFRUUF20cnJKS8vD/isbty4UV1djUKhRkdHBwcHUSgUBoMJDw9H/NPh4WEzMzNNTc3ftaePHj1iYGCATSoKhTp79ixCBvPs2TNycvL09HQCe7q8vOzk5ERJSYks//r6+oDjPjIyQk1NbWdnV1VVxcPDc+PGDRQKNTk5CVAp4IjY2dldvnwZjUYvLS0ZGBgICQkhaczflS+xp+Aeq6mplZeX29jYHD58GCZxYmLirVu3IiIiAAsWTobqywMHDoSHh6+srIyOjqqoqKSmpi4sLJSXl4+PjxPs+qurq/n4+OTk5AC56+eff0bIbbi4uKysrMDdu379urGx8czMjJaW1oULF8BTa29vP3fu3Eft6dTU1G7/1NbWVlZWtqurKyoqCvEo8Xi8o6MjKytrUlISBoOxs7O7dOkSVF3szkX09/dfunSJg4MDPs7BwUF5eXk+Pj40Gl1YWIjY0/LycrCnMGPAniLQNdPT06ysrCdOnHjw4AGsLgQyMjIiLi4O9hSDwbCxsUlISICL0d7efv36dW5uboJq0KqqKlpaWmFhYSiuGBsbExYW5uXl/fDhA7gGsGzMzMzo6+tfvnx5ampqeXkZXiV8k3p6erS0tAAwuFsGBgYUFBQUFBRgPaiqqpKSkrKyshofH9fU1JSUlARHwMLCgpmZeXh4eHFx0dDQUFhY+KMfpI+PDycnJzB3AZssYgR9fX2pqKhCQ0P3psVbWlquXLlCRUUlIyNTVFSkrq5+6NAhBQUFRFtHR0deXl7YF+Px+NnZWdjzAj6/s7PzpUuXYEHKysoC5Fk8Hv/8+fPjx48jAZ+JiYni4uKBgYGYmJjjx4+/fv16a2urtbWViYkJyOkIJCkpCbGnuw0c0MCcO3cOg8F8+PCBiYkJCRdsbW2Vl5ePjo4WFRWdPn0afovH46urq0VFRUNDQwcGBvT09ICvaWtrC/xTcFni4+O5ublhCVlfX2diYoLwAuIOg0UAchQkkbCzs5OSkrJ7mm1vb0NEPiQkpLe3V05Ojp2dvbu7GzYuv/zyy4MHD06ePGlubg7ZJBDkO33w4MGBAweMjIwcHR0fPnwoIiLCzMwcGhq6vr4+NTVlYmLCy8uLTPXFxcX+/n4MBhMREXHs2DFAwxseHn7w4AE4LntHlWC2MDIyQnZ+YmKCiorK3Nwcku/BwcHk5OSZmZl7/VNHR0dKSkpwON68eSMiIgKve3BwkJqa2t7e/t27d6ysrEpKSsivqqurgb7bxMSEgYGhs7NzYWFBX19fVFT0o9P4o/Il9rS4uJiDg+Pw4cPCwsKQd5KVlZ2YmHj9+vXJkyf5+fmVlZVv3bqloKAQHx+/vb3d2NjIwcFx4MABHh4ecCt6e3sjIiIgSUWQVGlra5OWliYmJhYVFZWRkfn2228FBAQSEhJsbW2JiIiYmZnLy8ujoqKOHj167NixtLS0nJycs2fPysrKuru7q6qq/u1vfzty5AiMHSLb29svXrw4cOAAvM6SkpILFy4QERH5+vqWl5dLS0tzcXG9ePHi9evXzMzMhoaGHz58wGKxbm5uREREUlJS+fn5u2P5a2trUVFRtLS00tLSb968efjwobS0dFRU1OjoqKOj4zfffKOlpdXY2Pj48WMSEhI+Pr66urrMzExKSkoqKqq3b9+CeV1fXzcwMDh8+DCBqogMDAxISEjs37/fzc3tl19+cXNzO3XqlJqaWl5enr29/aVLl+Lj4wkyzsADeurUKQsLi4qKCldXVx4envDw8NHRUT09PSIiogcPHgAtlYqKyoEDBx48eKCoqPjdd98xMDAUFhb29PSIi4v/4x//ePz4MUF/yMDAgIiICCMjY2JiYnNzs4aGhpSUVHd39+zsrK6uLhMTk7m5ua2tLQUFxQ8//ODj4zMzM6OrqwswzwSkFHg83sPDAyiSIFPMzs7Oz8+fkZHR0tIiJSV18eLFj4JQLC0tPXjwAIJxm5ubXl5eR48eRWwcuBL09PTh4eFwpL+/X1JSkpaWFhwiT0/Pn376ycXFJSsrKyYmhoKC4u7du52dnXFxcczMzOfOnXv06FFISIiUlJSfn9/4+Li5ufnPP/8cEhKCw+Hq6uqoqanV1dX3ahUcHHzy5EnIVMzOztLQ0MjLy8/Ozi4uLqqpqZ08eRIoZIAC1t3dvby8/OHDh6qqqiMjIwUFBcePH7e2tsbj8RgMxtfX9x//+EdoaChgKlNTUyclJc3NzT19+hTId4HHiYGBQUVFpbW1FfZS4uLiUKQF6QH4mmZnZ69evUpOTg6EtYmJiUZGRruXyZWVFRcXl3379kVGRjY3N/Pz89PT01dXV3d0dFhbW4OTy83NzcHB8dGK6czMzCNHjtDS0nZ2dvb19bGwsBw9ehSqXDY2Nt68eXPo0CETE5O6urqysjI3N7fo6GgsFvvs2bOjR49C+2JHR4eioiIypCkpKUVFRR+tsbW1tT18+DD4KGg0moaGRk9PD8h1Xr16RUxMHBcXh5SjwE8WFxcfPHhw7NgxyMIFBQWdP3/e09MTj8dPTk5SUlK6urp++PBBT0+PmJjY29u7o6MjKysLyvs2NjYUFRXp6OiamprW19dNTEy4uLj+ufZ0aWkpOTnZzs7Oz88vKirK09MzKChoeHg4PDz8xo0b1tbW9+7dMzExkZaWVlVVhehVWVkZBAodHR0hjVNWVnbjxo2rV6/u3YaUlJTY2dmZmppGRERYWlo6OTnFxcUFBAQ4OjoGBQW1t7dnZGQAbHhFRcXm5mZMTIympqaFhYWbm5uLi4udnV1sbOxun3d7ezsvL+/+/fuPHz8uLS2tq6vz9va2t7cvKCiYn58H6g57e3svLy8vLy/YHuJwuOrq6rt37+rr61dXVxOE8zY2Nl69eqWmpmZtbe3u7g44vl1dXY6OjtLS0g4ODtnZ2f7+/lJSUoaGhiUlJYGBgQoKCjdv3nz58iUs+Nvb20+fPtXS0oLx2S0QakSj0aGhoWJiYvfv36+vrx8ZGXn06JGenp6Xl5eDg0NISMhHC8WHh4fd3d1VVFTMzMy0tbVDQ0MXFxcbGhosLCykpaWtrKygjDE5OVlcXFxNTQ14yWVkZAAQ+t69ezIyMm5ubgTlvWg0OiYmRk1NTV1d/d69e7q6upBRBHIeMTExYWHh+/fvKykpXb58OSAgYGVlJSkpiZOTk5eXd689LSsrk5CQYGNjS0lJ2dzcTEtLk5SUVFJSMjExMTQ0TEpK+q2azYaGBm1tbbC2paWl5ubm8fHxeDwe0rJSUlL09PQaGhpQy/Xy5Utubm5wRubm5pKTk8nJya9evZqSkgIJCjY2tpiYmP7+/sjIyDNnzly8eBEA7RsbG1taWnh5eU+dOqWpqQmTjZGRkZ+fH3FjQbq7u3V1dSkoKMzNzbu6uiIjI1lYWHh4eFJTU2dnZz08PA4fPqyqqlpWVpaSkiIoKHj06FEODg51dfXg4OCOjg5nZ2dYV4qLizc2NlJTU8nJyZmZmc3NzYWFhQ8ePHjv3r3p6em0tDRiYmJWVtbi4uLW1lZFRcUff/xRXl7e1NT0yJEjly9fLi4uzsjIoKCg+O6770JDQ2EtfPPmDS0t7ZEjRwQEBCwsLHJychYXF5GPAoPBAPve2bNnra2tWVhY/va3v4WEhDQ3NzMzM0tJSZmZmdHS0urr63+0n2VwcPDevXtAZre5uQnwz0iF7Pj4uLKy8oEDByDJY2Vl1dTUVF5efv78eSIiIhUVlaqqKjc3t2+++YaUlDQrK6u9vf3ixYtInAqR5eVliPsTEREJCQm9ePHC3t6eiIiIhISksrKyuLiYnZ394MGDurq6CH0s/HBjYyMsLGz//v0iIiIxMTHq6urffvutsrJydXW1r6/v8ePHGRkZ29vbKyoqaGlpv/vuOx4entu3b/v7+4+NjUVERBw4cICIiMjY2PjFixdnzpwhIiJSU1Pby039UfnL+vffvXsnKysLTLkgb968kZGR+Wg3PYSWXV1d9wZQCCK+MAlWV1f3FvHsFojU/NZ1Pqcgua2tDVmKYfsAAMwEZmt3tHdiYqKqqgrZ18zMzLS1tbW1tQ0MDAwPD/f29ra2tkI+vbOzs7W1taWlpb+/H+CK+/r67t69Gx0dvXs/hdwCFF5cXOzs7Nw9oUdGRiorKxE0+4/K5uZmdXX169evKysrYd2emppqaWlpb2+vr6+H3P3Kygoog8fjgWhgcXFxeHi4ubkZHuGjUS3AzA8ICCBgjS0qKkpOTl5dXZ2amsrLy4NbYDCY5OTkkpKSj27oiouLIeYD/6yvrw8JCQkICEDIAX/r0QYGBkA3NBrd0dEB/U4bGxuFhYWhoaHBwcGBgYG1tbVLS0tpaWkhISEhISGxsbFTU1MTExMRERExMTHw7eXm5gYGBoLfAfU9QUFBr169glnU0tLy+PHjkJCQoKCgxMTE8PDwkJAQHx8fAgb2pqamyMjIgICAhISExsbGN2/ehIaGPnnyBIxXe3u7o6Ojm5sbFHVAKYKOjs67d+8wGExfX19ERERQUJC3t3dKSgoOh1teXvb19dXX13/9+nVqaqq7u3t0dPT6+vrk5KSLi4uxsTEEoysrK7W0tCwtLd++fevq6vrkyZOmpqacnBxglHny5Amga2Ox2OTkZCgSR8Ipuz+Evr4+W1tbHR2dmJiYwMBA4MtDo9HBwcFycnKSkpKGhoZIOwbBi1hdXW1tbYVACg6He/36NaSkkBM6OjpMTU3l5eXv3bsHsfWSkhIVFRVVVVUHB4eCgoKgoCAVFRU9Pb3Y2Nj6+npLS8uYmBiCb21xcdHLyws4AgwMDLy8vKysrIAHpampKS0tTVFR0cnJ6cmTJ9BSRFAna2tra21tHR8f7+Pjo66u/vTp08LCQj8/P2dn51u3blVVVe3s7CQlJamrqyspKQGHwtbWVnh4+K1bt1RVVW1sbAIDAzU0NG7fvo1Uu/+u/DX9png8Pi4uTkBAgJ+f38vLKz09PSAgQFdX18HB4bfsemZm5u3bt4FrkODinzB/H+3f+N0zP33BP9QTQpCq/gKpra21sbHR0tLi5+dHfOEvuMUX6/BnlCe4zucM/h868xPn/9YL/RdDXv3Jt/+Jy/6FV/vomPxRDwM58xMj/E8ajS+Q/xA1/jL/dHV1NSEhQUREhJaWlo6O7urVqxEREZ/ogxoeHgYKtr9Kgf8K2dzcDAkJIScnp6WljYyM/K9uyv4qX+WrEMhfY0+RqCIKhRoeHh4aGhofH0eMxV5vZWdn538T0wyHww0NDWVmZtbV1X0xJthX+Spf5T9T/kp7+vn/RVDA/xcKgTv8l+xH/hlK7v77n7pp+o/akf3lr+bTtyA48h8yDv878t8y4B+dNl92qf8OPOmNjY2BgYGJiYnPjCouLCz09PTgfu0Z//PvdXZ2FtzJf4YJ2K3hzMzMb7GEfvHF9x78q67/RzUhiHv+kwaT4Mhfe4uv8vny3zL4/1v2tLy8XEdHR0lJKSEh4XOiBJubmy9evJCSkgLEkL/kpdrb29va2kK5718r8C43NzcrKipMTEyUlJQyMjIIoCv+5MVXV1ezs7NdXV2fPn06ODj475rlOBxua2urqKgoKiqqt7f3n6QGFouF0iU/P7/3799jsdiFhYWMjAyoSfpn3PGrfEKmpqaam5s/E+bx3yjb29vT09MVFRX5+fl7Oag/X77Qnn7UnP+hL+Tzs40lJSXc3NyAXEWAQ0pwXySMGxYWJiYmVlpautfXI9gAfuZ229DQ0MDAAOkw+ejjb21tVVVVEdTr7b3dR58di8X+8ssvV69eJSIicnR0RGhFkPM/c6f80eOrq6tJSUkXL148d+7cb6E4Ly4uIkgFe0f1E5voT59JIBsbGwEBAdra2gD4sLW1tZvHYnJyEgF2+Og1P2eabW1tVVRU8PPzHz58ODg4eH19fXZ2FjDeoapmc3MTjUZDac5Hh5dAdp9DoAAGg/lDoJx7L/t/XvLz87W1tf8SqNl/qmCx2LS0NGFhYT4+vpycnC++zp+ql9ra2kLKJ5GDa2tre63Y7sqy3TPpM7NSMTExCgoKBF0Knyjj2Nra+jQzx+fYUPwuVaempj6KL7tb+vv71dXVkVb0z5TdatTU1Jw8eTIyMvJzTt598HOexcLCQlBQcDf5ByJYLDY9PX1v4T0iBJg1ny6g+bQa3d3dFRUV0BE7PT2dkJCArFIvX75MSEj4zOt84u6zs7PW1tZHjx59+fIlTLyMjIzk5GQMBgMArBkZGdCw8DnBgb0H4cj6+npeXt5exJCvsltqamqgH+ffrcjvyNbWVn5+/qVLl06ePPlntP1C/xSDwXR3d0MVdGNjI8QWAYX35cuXycnJAwMDYFWXl5erqqri4uJKS0vHxsbAgKLR6P7+/rKysoyMjNHR0d+1qklJSRoaGmlpaW1tbfX19QMDA0jV6tzcXFNTU1tbW1dX1+rq6vb2NgqF6u7uHhoa2trampubGx0dBYDYwcHB2trazs7O9fV1+CTQaHRvb29nZ2d7e/vY2NjIyAi0D+y2Hdvb2+Pj493d3VNTU4uLiygUanBwsK+vD4VCdXV1NTQ0zM7O4nC4gYEBe3v7K1euAHzB0NDQ6Ojo6Ojo8PBwR0cHeDHT09MNDQ21tbW9vb27HxmNRjc2NjY1NRUXF58+fbqkpGR2dravr29+fh4QZAYHB0dHR8EcwPnNzc21tbX9/f3IHnZ1dbWjo6Ompqanp2d3Nf7MzAx0p6ioqAgKCu4F8VxaWnr79q2cnJyDgwMC/j83N9fY2Pj+/XsEu4/AYVx